Triazine ring-containing polymer and film-forming composition containing the same
By using a combination of an arylamino-terminated triazine ring-containing polymer with crosslinking groups and an organic solvent, the problem of difficulty in preparing high refractive index and solvent-resistant films in low polarity solvents in the prior art is solved, and the problem of achieving the problem of achieving high refractive index and solvent-resistant films in low polarity solvents is achieved. Film preparation with high solubility, transparency and durability.
Patent Information
- Application Number
- CN202080074297.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-09
- Filing Date
- 2020-10-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-10-23
AI Technical Summary
The prior art is difficult to prepare films with high refractive index, transparency and solvent resistance in low polar solvents, and polymers are prone to cracks when the solvent is exposed, affecting their durability.
Using a triazine ring-containing polymer having at least one triazine ring end and a portion of the triazine ring end is formed by an arylamino-terminated triazine ring with crosslinking groups, a high refractive index and resistance are formed by using in combination with an organic solvent. Solvent-based film.
High solubility and high transparency in low-polar solvents are achieved, pipeline blockage problems are avoided, and crack resistance and durability of the film are improved.
Smart Images

Figure CN114599704B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a triazine ring-containing polymer and a film-forming composition containing the polymer. Background Art
[0002] In recent years, high-functional polymer materials are needed in the development of electronic devices such as liquid crystal displays, organic electroluminescent (EL) elements (organic EL displays or organic EL lighting), touch panels, optical semiconductor (LED) elements, solid-state imaging elements, organic thin-film solar cells, dye-sensitized solar cells, and organic thin-film transistors (TFTs).
[0003] Specific required properties include 1) heat resistance, 2) transparency, 3) high refractive index, 4) high solubility, 5) low volume shrinkage, 6) high temperature and high humidity resistance, and 7) high film hardness.
[0004] In view of this aspect, the applicant has found that a polymer containing repeating units having a triazine ring and an aromatic ring has a high refractive index, and the polymer alone can achieve high heat resistance, high transparency, high refractive index, high solubility and low volume shrinkage, and is suitable as a film-forming composition for manufacturing electronic devices (Patent Document 1).
[0005] In organic EL lighting, a composition in which a high refractive index material is dissolved in an organic solvent is generally used to form a thin film in a planarizing layer or a light scattering layer by a coating method. However, depending on the type of transparent conductive film, a highly polar solvent may not be used.
[0006] In addition, after coating a film-forming composition containing a high refractive polymer using a coating device, a low-polarity solvent or the like may be used as a solvent for cleaning the pipeline of the device. However, a polymer with low solubility in such a solvent may cause pipeline clogging. In addition, when a thin film is exposed to a solvent during the manufacture of electronic devices, cracks may occur in the produced thin film depending on the conditions, and further improvement of its durability is required.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent document 1: International Publication No. 2010 / 128661. Summary of the invention
[0010] Problems to be solved by the invention
[0011] The present invention has been made in view of the above circumstances, and its object is to provide a triazine ring-containing polymer and a film-forming composition containing the polymer, which can form a thin film having a high refractive index and excellent transparency and solvent resistance (crack resistance) and has excellent solubility in various organic solvents such as low-polarity solvents, hydrophobic solvents, and low-boiling point solvents.
[0012] Technical solutions to problems
[0013] As a result of intensive studies to achieve the above-mentioned object, the present inventors have found that by using a triazine ring-containing polymer having at least one triazine ring terminal and at least a part of the triazine ring terminal being capped with an aromatic amino group having a crosslinking group, a triazine ring-containing polymer that can form a film having a high refractive index and excellent transparency and solvent resistance and has excellent solubility in various organic solvents can be obtained, thereby completing the present invention.
[0014] That is, the present invention provides the following triazine ring-containing polymer and a film-forming composition containing the polymer.
[0015] [1]. A polymer containing a triazine ring, characterized in that:
[0016] The present invention contains a repeating unit structure represented by the following formula (1), has at least one triazine ring terminal, and at least a part of the triazine ring terminal is blocked with an aromatic amino group having a crosslinking group.
[0017]
[0018] {wherein, R and R' independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group or an aralkyl group,
[0019] Ar represents at least one selected from the group represented by formulae (2) to (13).
[0020]
[0021] 〔In the formula, R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a sulfo group, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms,
[0022] R 93 and R 94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms,
[0023] W 1 and W 2 Independently represent single bonds, CR 95 R 96 (R 95 and R 96independently represent a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (however, these may form a ring together), C═O, O, S, SO, SO2 or NR 97 (R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group),
[0024] X 1 and X 2 each independently represents a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the formula (14),
[0025]
[0026] (Where R 98 ~R 101 each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a sulfo group, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms,
[0027] Y 1 and Y 2 Each of them independently represents a single bond or an alkylene group having 1 to 10 carbon atoms.
[0028] [2] A triazine ring-containing polymer as described in [1], wherein:
[0029] The R 1 ~R 92 and R 98 ~R 101 They are independently a hydrogen atom, a halogen atom or a halogenated alkyl group having 1 to 10 carbon atoms.
[0030] [3] A triazine ring-containing polymer as described in [1] or [2], wherein:
[0031] The aromatic amino group having the crosslinking group is represented by formula (15).
[0032]
[0033] (Where R 102 represents a cross-linking group. )
[0034] [4] A triazine ring-containing polymer as described in [3], wherein:
[0035] The aromatic amino group having the crosslinking group is represented by formula (16).
[0036]
[0037] (Where R 102 Means the same as above.)
[0038] [5] A triazine ring-containing polymer as described in any one of [1] to [4], wherein
[0039] The crosslinking group is a hydroxyl group-containing group or a (meth)acryloyl group-containing group.
[0040] [6]. A triazine ring-containing polymer as described in [5], wherein:
[0041] The crosslinking group is a hydroxyalkyl group, a (meth)acryloyloxyalkyl group, or a group represented by the following formula (i).
[0042]
[0043] (In the formula, A 1 represents an alkylene group having 1 to 10 carbon atoms, A 2 represents a single bond or a group represented by the following formula (j),
[0044]
[0045] A 3 represents a divalent or trivalent aliphatic hydrocarbon group which may be substituted by a hydroxyl group, A 4 represents a hydrogen atom or a methyl group, a represents 1 or 2, and * represents a chemical bond. )
[0046] [7]. A triazine ring-containing polymer as described in [6], wherein:
[0047] The crosslinking group is one or more selected from a hydroxymethyl group, a 2-hydroxyethyl group, a (meth)acryloyloxymethyl group, a (meth)acryloyloxyethyl group, and a group represented by the following formula (i-2) to (i-5).
[0048]
[0049] (In the formula, * represents a chemical bond.)
[0050] [8] A triazine ring-containing polymer as described in any one of [1] to [7], wherein:
[0051] At least one aromatic ring in Ar contains at least one halogen atom or a halogenated alkyl group having 1 to 10 carbon atoms.
[0052] [9]. A triazine ring-containing polymer as described in any one of [1] to [8], wherein:
[0053] A portion of the triazine ring terminals are further capped with unsubstituted arylamino groups.
[0054]
[10] . A triazine ring-containing polymer as described in any one of [1] to [9], wherein:
[0055] The unsubstituted arylamino group is represented by formula (33).
[0056]
[0057]
[11] . A triazine ring-containing polymer as described in any one of [1] to
[10] , wherein:
[0058] The Ar is represented by formula (17).
[0059]
[0060]
[12] . A triazine ring-containing polymer as described in any one of [1] to
[10] , wherein:
[0061] The Ar is represented by formula (20).
[0062]
[0063]
[13] . A film-forming composition, wherein:
[0064] Contains any one of the triazine ring-containing polymers [1] to
[12] and an organic solvent.
[0065]
[14] . The film-forming composition according to
[13] , wherein
[0066] The organic solvent contains at least one selected from glycol ester solvents, ketone solvents, and ester solvents.
[0067]
[15] . The film-forming composition according to
[13] or
[14] , wherein
[0068] It also contains a cross-linking agent.
[0069]
[16] . The film-forming composition according to
[15] , wherein
[0070] The crosslinking agent is a multifunctional (meth)acrylic compound.
[0071]
[17] . A film, wherein
[0072] The thin film is obtained from the film-forming composition according to any one of
[13] to
[16] .
[0073]
[18] . An electronic device, wherein:
[0074] A substrate and a thin film of
[17] formed on the substrate.
[0075]
[19] . An optical component, wherein:
[0076] A substrate and a thin film of
[17] formed on the substrate.
[0077] Effects of the Invention
[0078] According to the present invention, a triazine ring-containing polymer can be provided which can form a thin film having a high refractive index and excellent transparency and solvent resistance and has excellent solubility in various organic solvents such as low polarity solvents, hydrophobic solvents, and low boiling point solvents.
[0079] By using such a triazine ring-containing polymer of the present invention, a composition can be prepared using an organic solvent with low solubility such as a low-polarity solvent or a hydrophobic solvent, and thus a thin film can be formed without problems even on a substrate that is easily corroded by a high-polarity solvent.
[0080] Since the thin film made from the film-forming composition of the present invention can exhibit properties such as high heat resistance, high refractive index, low volume shrinkage, and solvent resistance (crack resistance), it can be used in the field of electronic devices or optical materials such as a component when making liquid crystal displays, organic EL elements (organic EL displays or organic EL lighting), touch panels, optical semiconductors (LED) elements, solid-state imaging elements, organic thin-film solar cells, dye-sensitized solar cells, organic thin-film transistors (TFTs), lenses, prisms, cameras, binoculars, microscopes, semiconductor exposure devices, etc.
[0081] In particular, since the thin film made from the film-forming composition of the present invention has high transparency and high refractive index and solvent resistance (crack resistance), it can be used as a flattening layer or light scattering layer for organic EL lighting to improve its light extraction efficiency (light diffusion efficiency) and its durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 is the compound P-1 (polymer compound [4]) obtained in Example 1-1 1 H-NMR spectrum.
[0083] Figure 2 is the compound P-2 (polymer compound [5]) obtained in Example 1-2 1 H-NMR spectrum.
[0084] Figure 3 is the compound P-3 (polymer compound [7]) obtained in Example 1-3 1 H-NMR spectrum.
[0085] Figure 4 Compound P-4 (polymer compound [8]) obtained in Comparative Example 1-1 1 H-NMR spectrum.
[0086] Figure 5The compound P-5 (polymer compound [9]) obtained in Comparative Example 1-2 1 H-NMR spectrum.
[0087] Figure 6 is the compound P-6 (polymer compound
[10] ) obtained in Example 1-4 1 H-NMR spectrum.
[0088] Figure 7 This is an optical microscope photograph of the surface of the cured film obtained in Example 2-1 after solvent exposure.
[0089] Figure 8 This is an optical microscope photograph of the surface of the cured film obtained in Example 2-2 after solvent exposure.
[0090] Fig. 9 This is an optical microscope photograph of the surface of the cured film obtained in Example 2-3 after solvent exposure.
[0091] Fig.10 This is an optical microscope photograph of the surface of the cured film obtained in Comparative Example 2-1 after solvent exposure.
[0092] Fig.11 This is an optical microscope photograph of the surface of the cured film obtained in Comparative Example 2-2 after solvent exposure.
[0093] Fig.12 is the compound P-11 (polymer compound
[15] ) obtained in Example 3-1 1 H-NMR spectrum.
[0094] Fig.13 is the compound P-12 (polymer compound
[16] ) obtained in Example 3-2 1 H-NMR spectrum.
[0095] Fig.14 The compound P-13 (polymer compound
[19] ) obtained in Comparative Example 3-1 1 H-NMR spectrum.
[0096] Fig.15 This is an optical microscope photograph of the surface of the cured film obtained in Example 3-1.
[0097] Fig.16 This is an optical microscope photograph of the surface of the cured film obtained in Comparative Example 3-1.
[0098] Fig.17 is the compound P-22 (polymer compound
[104] ) obtained in Example 5-2 1H-NMR spectrum.
[0099] Fig.18 This is an optical microscope photograph of the surface of the cured film obtained in Example 6-1 after being exposed to the solvent.
[0100] Fig.19 This is an optical microscope photograph of the surface of the cured film obtained in Example 6-2 after being exposed to the solvent. DETAILED DESCRIPTION
[0101] Hereinafter, the present invention will be described in further detail.
[0102] The triazine ring-containing polymer of the present invention contains a repeating unit structure represented by the following formula (1).
[0103] The polymer containing triazine rings is, for example, a so-called hyperbranched polymer. A hyperbranched polymer is a highly branched polymer having an irregular branch structure. The irregularity mentioned here means that the branch structure is more irregular than that of a dendrimer, which is a highly branched polymer having a regular branch structure.
[0104] For example, in a triazine ring-containing polymer as a hyperbranched polymer, a structure (structure A) in which three chemical bonds of the repeating unit structure represented by formula (1) are respectively bonded to the repeating unit structure represented by formula (1) is included as a structure larger than the repeating unit structure represented by formula (1). In the triazine ring-containing polymer as a hyperbranched polymer, structure A is distributed throughout the entire triazine ring-containing polymer except for the terminal.
[0105] In the triazine ring-containing polymer as a hyperbranched polymer, the repeating unit structure may be essentially only the repeating unit structure represented by formula (1).
[0106]
[0107] In the above formula, R and R' independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group or an aralkyl group. From the viewpoint of further increasing the refractive index, a hydrogen atom is preferred.
[0108] In the present invention, the number of carbon atoms in the alkyl group is not particularly limited, but is preferably 1 to 20. In order to further improve the heat resistance of the polymer, the number of carbon atoms in the alkyl group is more preferably 1 to 10, and further preferably 1 to 3. In addition, the structure of the alkyl group is not particularly limited, and may be, for example, chain, branched, cyclic, or a combination of two or more thereof.
[0109] Specific examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, 1-methyl-cyclopropyl, 2-methyl-cyclopropyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclo ... -methyl-cyclobutyl, 1,2-dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl Butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl cyclopropyl, 2-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl, 2-ethyl-3-methyl-cyclopropyl, etc.
[0110] The number of carbon atoms in the alkoxy group is not particularly limited, but is preferably 1 to 20. In order to further improve the heat resistance of the polymer, the number of carbon atoms in the alkoxy group is more preferably 1 to 10, and further preferably 1 to 3. The structure of the alkyl portion is not particularly limited, and may be, for example, chain, branched, cyclic, or a combination of two or more thereof.
[0111] Specific examples of the alkoxy group include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, 1-methyl-n-butoxy, 2-methyl-n-butoxy, 3-methyl-n-butoxy, 1,1-dimethyl-n-propoxy, 1,2-dimethyl-n-propoxy, 2,2-dimethyl-n-propoxy, 1-ethyl-n-propoxy, n-hexyloxy, 1-methyl-n-pentoxy, 2-methyl-n-pentoxy, 3-methyl-n-pentoxy , 4-methyl-n-pentoxy, 1,1-dimethyl-n-butoxy, 1,2-dimethyl-n-butoxy, 1,3-dimethyl-n-butoxy, 2,2-dimethyl-n-butoxy, 2,3-dimethyl-n-butoxy, 3,3-dimethyl-n-butoxy, 1-ethyl-n-butoxy, 2-ethyl-n-butoxy, 1,1,2-trimethyl-n-propoxy, 1,2,2-trimethyl-n-propoxy, 1-ethyl-1-methyl-n-propoxy, 1-ethyl-2-methyl-n-propoxy, etc.
[0112] The number of carbon atoms in the aryl group is not particularly limited, but is preferably 6 to 40. In order to further improve the heat resistance of the polymer, the number of carbon atoms in the aryl group is more preferably 6 to 16, and even more preferably 6 to 13.
[0113] In the present invention, the aryl group includes an aryl group having a substituent. Examples of the substituent include a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, and a cyano group.
[0114] Specific examples of the aryl group include phenyl, o-chlorophenyl, m-chlorophenyl, p-chlorophenyl, o-fluorophenyl, p-fluorophenyl, o-methoxyphenyl, p-methoxyphenyl, p-nitrophenyl, p-cyanophenyl, α-naphthyl, β-naphthyl, o-biphenyl, m-biphenyl, p-biphenyl, 1-anthryl, 2-anthryl, 9-anthryl, 1-phenanthryl, 2-phenanthryl, 3-phenanthryl, 4-phenanthryl, 9-phenanthryl and the like.
[0115] The number of carbon atoms in the aralkyl group is not particularly limited, but is preferably 7 to 20. The structure of the alkyl portion is not particularly limited, and may be, for example, linear, branched, cyclic, or a combination of two or more thereof.
[0116] In the present invention, the aralkyl group includes an aralkyl group having a substituent. Examples of the substituent include a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, and a cyano group.
[0117] Specific examples thereof include benzyl, p-methylphenylmethyl, m-methylphenylmethyl, o-ethylphenylmethyl, m-ethylphenylmethyl, p-ethylphenylmethyl, 2-propylphenylmethyl, 4-isopropylphenylmethyl, 4-isobutylphenylmethyl and α-naphthylmethyl.
[0118] The above-mentioned Ar represents at least one selected from the group represented by formulae (2) to (13).
[0119]
[0120] The above R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a sulfo group, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, and R 93 and R 94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, W 1 and W 2 Independently represent single bonds, CR 95 R 96 (R 95 and R 96 independently represent a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (however, these may form a ring together), C═O, O, S, SO, SO2 or NR 97 (R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group).
[0121] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0122] In addition, examples of the alkyl group and the alkoxy group include the same groups as the alkyl group and the alkoxy group in R and R′.
[0123] The halogenated alkyl group having 1 to 10 carbon atoms is obtained by replacing at least one hydrogen atom in the alkyl group having 1 to 10 carbon atoms with a halogen atom, and specific examples thereof include trifluoromethyl, 2,2,2-trifluoroethyl, perfluoroethyl, 3,3,3-trifluoropropyl, 2,2,3,3,3-pentafluoropropyl, 2,2,3,3-tetrafluoropropyl, 2,2,2-trifluoro-1-(trifluoromethyl)ethyl, perfluoropropyl, 4,4,4-trifluorobutyl, 3,3,4, 4,4-pentafluorobutyl, 2,2,3,3,4,4,4-heptafluorobutyl, perfluorobutyl, 2,2,3,3,4,4,5,5,5-nonafluoropentyl, 2,2,3,3,4,4,5,5-octafluoropentyl, perfluoropentyl, 2,2,3,3,4,4,5,5,6,6,6-undecafluorohexyl, 2,2,3,3,4,4,5,5,6,6-decafluorohexyl, 3,3,4,4,5,5,6,6,6-nonafluorohexyl and perfluorohexyl. In the present invention, in view of improving the solubility of the triazine ring-containing polymer in a low-polarity solvent while maintaining the refractive index, a perfluoroalkyl group having 1 to 10 carbon atoms is preferred, and a perfluoroalkyl group having 1 to 5 carbon atoms is more preferred, and a trifluoromethyl group is further preferred.
[0124] In addition, X 1 and X 2 Each of them independently represents a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the formula (14).
[0125] The structures of these alkyl groups, halogenated alkyl groups, alkoxy groups and alkylene groups are not particularly limited, and may be, for example, chain-like, branched, cyclic, or a combination of two or more thereof.
[0126]
[0127] The above R 98 ~R 101 each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a sulfo group, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, and Y 1 and Y 2 Each of the halogen atoms, alkyl groups, halogenated alkyl groups and alkoxy groups is independently a single bond or an alkylene group having 1 to 10 carbon atoms. 1 ~R 92 The halogen atom, alkyl group, haloalkyl group and alkoxy group are the same groups.
[0128] Examples of the alkylene group having 1 to 10 carbon atoms include a methylene group, an ethylene group, a propylene group, a trimethylene group, a tetramethylene group, and a pentamethylene group.
[0129] The structure of the alkylene group is not particularly limited, and may be, for example, a chain, a branched, a cyclic, or a combination of two or more thereof.
[0130] Among them, as R 1 ~R 92 and R 98 ~R 101 , preferably a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 5 carbon atoms, a haloalkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms, and more preferably a hydrogen atom.
[0131] In the triazine ring-containing polymer of the present invention, it is preferred that at least one of the aromatic rings included in the above-mentioned Ar contains at least one halogen atom or a halogenated alkyl group having 1 to 10 carbon atoms. Generally, it is known that the refractive index tends to decrease by introducing fluorine atoms into a compound, but the triazine ring-containing polymer of the present invention still maintains a refractive index of more than 1.7 although fluorine atoms are also introduced. The number of halogen atoms or halogenated alkyl groups in the aromatic ring can be any number that can be substituted on the aromatic ring, but considering the balance between the refractive index and the solubility in the solvent, it is preferably 1 to 4, more preferably 1 to 2, and even more preferably 1. It should be noted that in the case where the aromatic ring is a substance in which multiple aromatic rings are fused, such as a naphthalene ring, it is sufficient to have at least one of the above-mentioned groups as a whole.
[0132] When Ar contains multiple aromatic rings, at least one aromatic ring may contain at least one halogen atom or halogenated alkyl group, but preferably all aromatic rings contain at least one halogen atom or halogenated alkyl group, and more preferably all aromatic rings contain one halogen atom or halogenated alkyl group.
[0133] In particular, Ar is preferably at least one of the groups represented by formulae (2), (5) to (13), and more preferably at least one of the groups represented by formulae (2), (5), (7), (8), (11) to (13). Specific examples of the aryl group represented by formulae (2) to (13) include groups represented by the following formulae, but are not limited thereto.
[0134]
[0135] "Ph" means phenyl.
[0136]
[0137] (In the formula, A is independently a halogen atom or a halogenated alkyl group having 1 to 10 carbon atoms, p is independently an integer of 0 to 4, q is independently an integer of 0 to 3, r is independently an integer of 0 to 2, s is independently an integer of 0 to 5, t is an integer of 1 to 6, and u is an integer of 1 to 4. However, in each group, the total of p, q, r, and s is 1 or more. "Ph" represents a phenyl group.)
[0138] Among them, an aryl group represented by the following formula is more preferable because a polymer having a higher refractive index can be obtained.
[0139]
[0140] "Ph" means phenyl.
[0141]
[0142] (In the formula, A, p, q, r and u have the same meanings as above. "Ph" represents a phenyl group.)
[0143] In particular, from the viewpoint of further improving the solubility of the triazine ring-containing polymer in an organic solvent such as a low-polarity solvent, Ar is preferably a meta-phenylene group represented by the formula (17).
[0144]
[0145] In particular, from the viewpoint of further increasing the refractive index of the triazine ring-containing polymer, as Ar, a group having a diphenyl ether skeleton represented by formulae (18) to (20) is preferred.
[0146]
[0147] (In the formula, A and p have the same meanings as above.)
[0148]
[0149] (In the formula, A and p have the same meanings as above.)
[0150]
[0151] In addition, the triazine ring-containing polymer of the present invention has at least one triazine ring terminal, and at least a part of the triazine ring terminal is blocked with an aromatic amino group having a crosslinking group.
[0152] It should be noted that the triazine ring-containing polymer of the present invention has at least one triazine ring terminal, and the triazine ring at the terminal generally has two halogen atoms that can be substituted by the arylamino group having the above-mentioned crosslinking group. Therefore, the arylamino group having the above-mentioned crosslinking group can be bonded to the same triazine ring terminal, and in the case of having multiple triazine ring terminals, they can be bonded to different triazine ring terminals respectively.
[0153] Examples of the aryl group of the arylamino group having the crosslinking group include the same groups as described above, and a phenyl group is particularly preferred.
[0154] It should be noted that the cross-linking group is bonded to the aromatic group.
[0155] Examples of the crosslinking group include a hydroxyl-containing group, a vinyl-containing group, an epoxy-containing group, an oxetane-containing group, a carboxyl-containing group, a sulfone-containing group, a thiol-containing group, a (meth)acryloyl-containing group, and the like. In view of improving the heat resistance of the triazine ring-containing polymer and the solvent resistance (crack resistance) of the obtained film, a hydroxyl-containing group and a (meth)acryloyl-containing group are preferred.
[0156] Examples of the hydroxyl group-containing group include hydroxyl groups and hydroxyalkyl groups, and a hydroxyalkyl group having 1 to 10 carbon atoms is preferred, a hydroxyalkyl group having 1 to 5 carbon atoms is more preferred, and a hydroxyalkyl group having 1 to 3 carbon atoms is further preferred.
[0157] Examples of the hydroxyalkyl group having 1 to 10 carbon atoms include hydroxymethyl, 2-hydroxyethyl, 3-hydroxypropyl, 4-hydroxybutyl, 5-hydroxypentyl, 6-hydroxyhexyl, 7-hydroxyheptyl, 8-hydroxyoctyl, 9-hydroxynonyl, 10-hydroxydecyl, 2-hydroxy-1-methylethyl, 2-hydroxy-1,1-dimethylethyl, 3-hydroxy-1-methylpropyl, 3-hydroxy-2-methylpropyl, 3-hydroxy-1,1-dimethylpropyl, 3-hydroxy-1,2-dimethylpropyl, 3-hydroxy-2,2-dimethyl A group in which the carbon atom to which the hydroxyl group is bonded, such as propyl, 4-hydroxy-1-methylbutyl, 4-hydroxy-2-methylbutyl, and 4-hydroxy-3-methylbutyl, is a primary carbon atom; a group in which the carbon atom to which the hydroxyl group is bonded, such as 1-hydroxyethyl, 1-hydroxypropyl, 2-hydroxypropyl, 1-hydroxybutyl, 2-hydroxybutyl, 1-hydroxyhexyl, 2-hydroxyhexyl, 1-hydroxyoctyl, 2-hydroxyoctyl, 1-hydroxydecyl, 2-hydroxydecyl, 1-hydroxy-1-methylethyl, and 2-hydroxy-2-methylpropyl, is a secondary or tertiary carbon atom.
[0158] In particular, in view of improving heat resistance and high-temperature and high-humidity resistance, a group in which the carbon atom to which the hydroxyl group is bonded is a primary carbon atom is preferred, among which a hydroxyalkyl group having 1 to 5 carbon atoms is more preferred, a hydroxyalkyl group having 1 to 3 carbon atoms is further preferred, a hydroxymethyl group and a 2-hydroxyethyl group are further preferred, and a 2-hydroxyethyl group is most preferred.
[0159] Examples of the group containing a (meth)acryloyl group include a (meth)acryloyl group, a (meth)acryloyloxyalkyl group, and a group represented by the following formula (i). A (meth)acryloyloxyalkyl group having an alkylene group having 1 to 10 carbon atoms and a group represented by the following formula (i) are preferred, and a group represented by the following formula (i) is more preferred.
[0160]
[0161] (In the formula, A 1 represents an alkylene group having 1 to 10 carbon atoms, A 2 represents a single bond or a group represented by the following formula (j),
[0162]
[0163] A 3 represents a divalent or trivalent aliphatic hydrocarbon group which may be substituted by a hydroxyl group, A 4 represents a hydrogen atom or a methyl group, a represents 1 or 2, and * represents a chemical bond. )
[0164] Examples of the alkylene group included in the (meth)acryloyloxyalkyl group having an alkylene group (alkanediyl group) having 1 to 10 carbon atoms include methylene, ethylene, trimethylene, propane-1,2-diyl, tetramethylene, butane-1,3-diyl, butane-1,2-diyl, 2-methylpropane-1,3-diyl, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, etc. In view of improving heat resistance and high temperature and high humidity resistance, an alkylene group having 1 to 5 carbon atoms is preferred, an alkylene group having 1 to 3 carbon atoms is preferred, and an alkylene group having 1 or 2 carbon atoms is more preferred.
[0165] Specific examples of the (meth)acryloyloxyalkyl group include a (meth)acryloyloxymethyl group, a 2-(meth)acryloyloxyethyl group, a 3-(meth)acryloyloxypropyl group, and a 4-(meth)acryloyloxybutyl group.
[0166] In formula (i), A 1 It is an alkylene group having 1 to 10 carbon atoms, preferably an alkylene group having 1 to 5 carbon atoms, and more preferably a methylene group and an ethylene group. Examples of the alkylene group having 1 to 10 carbon atoms include the same groups as those included in the above-mentioned (meth)acryloyloxyalkyl group.
[0167] A 2 represents a single bond or a group represented by the formula (j), and a group represented by the formula (j) is preferred.
[0168] A 3 is a divalent or trivalent aliphatic hydrocarbon group which may be substituted with a hydroxyl group, and specific examples thereof include an alkylene group having 1 to 5 carbon atoms and groups represented by the following formulae (k-1) to (k-3),
[0169]
[0170] (In the formula, * is the same as above.)
[0171] An alkylene group having 1 to 5 carbon atoms is preferred, an alkylene group having 1 to 3 carbon atoms is more preferred, and a methylene group and an ethylene group are still more preferred. 3 The alkylene group includes A 1 The alkylene groups listed in are alkylene groups having 1 to 5 carbon atoms.
[0172] a represents 1 or 2, and is preferably 1.
[0173] As a preferred embodiment of the group represented by the formula (i), there can be mentioned an embodiment represented by the following formula (i-1).
[0174]
[0175] (In the formula, A 1 , A 3 , A 4 Same as *. )
[0176] As a more preferable embodiment of the group represented by the formula (i), embodiments represented by the following formulae (i-2) to (i-5) are mentioned.
[0177]
[0178] (In the formula, * is the same as above.)
[0179] Examples of the vinyl group include alkenyl groups having 2 to 10 carbon atoms and having a vinyl group at the terminal, and specific examples include vinyl, 1-propenyl, allyl, isopropenyl, 1-butenyl, 2-butenyl, and 2-pentenyl.
[0180] Examples of the epoxy group-containing group include epoxy group, glycidyl group, glycidyloxy group, etc. Specific examples include glycidylmethyl group, 2-glycidylethyl group, 3-glycidylpropyl group, 4-glycidylbutyl group, etc.
[0181] Examples of the oxetane-containing group include oxetan-3-yl, (oxetan-3-yl)methyl, 2-(oxetan-3-yl)ethyl, 3-(oxetan-3-yl)propyl, and 4-(oxetan-3-yl)butyl.
[0182] Examples of the carboxyl group-containing group include a carboxyl group and a carboxylalkyl group having 2 to 10 carbon atoms. As the carboxylalkyl group having 2 to 10 carbon atoms, it is preferred that the carbon atom to which the carboxyl group is bonded is a primary carbon atom, and specific examples thereof include a carboxylmethyl group, a 2-carboxyethyl group, a 3-carboxypropyl group, and a 4-carboxybutyl group.
[0183] Examples of the sulfo group-containing group include a sulfo group and a sulfoalkyl group having 1 to 10 carbon atoms. As the sulfoalkyl group having 1 to 10 carbon atoms, the carbon atom to which the sulfo group is bonded is preferably a primary carbon atom, and specific examples thereof include a sulfomethyl group, a 2-sulfoethyl group, a 3-sulfopropyl group, and a 4-sulfobutyl group.
[0184] Examples of the thiol-containing group include a thiol group and a mercaptoalkyl group having 1 to 10 carbon atoms. As the mercaptoalkyl group having 1 to 10 carbon atoms, it is preferred that the carbon atom to which the thiol group is bonded is a primary carbon atom, and specific examples thereof include a mercaptomethyl group, a 2-mercaptoethyl group, a 3-mercaptopropyl group, and a 4-mercaptobutyl group.
[0185] The number of crosslinking groups in the arylamino group having the crosslinking group is not particularly limited and can be any number that can be substituted on the aryl group. In consideration of the balance between solvent resistance and solubility in solvents, the number is preferably 1 to 4, more preferably 1 to 2, and even more preferably 1.
[0186] Examples of the arylamino group having a suitable crosslinking group include a group represented by formula (15), and a group represented by formula (16) having a crosslinking group at the para position of the amino group is particularly preferred.
[0187]
[0188] (Where R 102 represents a cross-linking group. )
[0189]
[0190] (Where R 102 Means the same as above.)
[0191] Specific examples of the arylamino group having a crosslinking group include groups represented by the following formulae, but are not limited to these.
[0192]
[0193] In addition, in the production method described later, an arylamino group having a hydroxyalkyl group can be introduced using a corresponding arylamino compound substituted with a hydroxyalkyl group.
[0194] Specific examples of the hydroxyalkyl-substituted arylamino compound include (4-aminophenyl)methanol and 2-(4-aminophenyl)ethanol.
[0195] The arylamino group having a (meth)acryloyloxyalkyl group can be introduced by a method using a corresponding (meth)acryloyloxyalkyl-substituted arylamino compound, or by a method of introducing an arylamino group having a hydroxyalkyl group into a triazine ring-containing polymer and then allowing a (meth)acryloyl halide or glycidyl (meth)acrylate to act on the hydroxyl group contained in the hydroxyalkyl group.
[0196] The arylamino group having a group represented by formula (i) can be introduced by the following method: a method using an arylamino compound having a target crosslinking group, or a method in which an arylamino group having a hydroxyalkyl group is introduced into a triazine ring-containing polymer and then a (meth)acrylate compound having an isocyanate group represented by the following formula (i') is allowed to act on the hydroxyl group contained in the above hydroxyalkyl group.
[0197]
[0198] (In the formula, A 3 , A 4 Same as a.)
[0199] Specific examples of the (meth)acryloyloxyalkyl-substituted arylamino compound include ester compounds obtained by reacting a hydroxyl group of the above-mentioned hydroxyalkyl-substituted arylamino compound with a (meth)acryloyl halide or glycidyl (meth)acrylate.
[0200] Examples of the (meth)acryloyl halide include (meth)acryloyl chloride, (meth)acryloyl bromide and (meth)acryloyl iodide.
[0201] Specific examples of the (meth)acrylate compound having an isocyanate group represented by the above formula (i') include 2-isocyanatoethyl acrylate, 2-isocyanatoethyl methacrylate, and 1,1-(bisacryloyloxymethyl)ethyl isocyanate. In the present invention, 2-isocyanatoethyl acrylate is preferred from the viewpoint of a simple synthesis method.
[0202] In the present invention, particularly suitable triazine ring-containing polymers include polymers containing repeating units represented by formulae (21) to (28).
[0203]
[0204] (In the formula, R, R', R 1 ~R 4 and R 102 Means the same as above.)
[0205]
[0206] (Where R 1 ~R 4 and R 102 Means the same as above.)
[0207]
[0208] (Where R 102 Means the same as above.)
[0209]
[0210] (Where R 102 Means the same as above.)
[0211]
[0212] (In the formula, R, R', R 16 ~R 23 and R 102 Means the same as above.)
[0213]
[0214] (Where R 16 ~R 23 and R 102 Means the same as above.)
[0215]
[0216] (Where R 102 Means the same as above.)
[0217]
[0218] (Where R 102 Means the same as above.)
[0219] The weight average molecular weight of the polymer in the present invention is not particularly limited, but is preferably 500 to 500,000, more preferably 500 to 100,000. From the perspective of further improving heat resistance and reducing shrinkage, it is preferably 2,000 or more. From the perspective of further improving solubility and reducing the viscosity of the obtained solution, it is preferably 50,000 or less, more preferably 30,000 or less, further preferably 25,000 or less, and most preferably 10,000 or less.
[0220] In addition, the weight average molecular weight in the present invention is an average molecular weight obtained by gel permeation chromatography (hereinafter referred to as GPC) analysis and converted into standard polystyrene.
[0221] The triazine ring-containing polymer (hyperbranched polymer) of the present invention can be produced according to the method disclosed in the above-mentioned International Publication No. 2010 / 128661.
[0222] That is, after a trihalogenated triazine compound is reacted with an aryl diamino compound in an organic solvent, for example, at least one aryl amino compound selected from an aryl amino compound having a hydroxyalkyl group (a hydroxyl-containing group), an aryl amino compound having an acryloyloxyalkyl group (an acryloyl-containing group), and an aryl amino compound having a group represented by formula (i) (an acryloyl-containing group) is reacted as a terminal blocking agent, thereby being able to obtain the triazine ring-containing polymer of the present invention.
[0223] For example, as shown in the following Scheme 1, a triazine ring-containing polymer (23) can be obtained by reacting a triazine compound (29) and an aryl diamino compound (30) in an appropriate organic solvent, and then reacting the triazine compound (29) and an aryl diamino compound (30) with at least one aryl amino compound (31) selected from an aryl amino compound having a hydroxyalkyl group and an aryl amino compound having a group represented by formula (i) as a terminal blocking agent.
[0224] Solution 1
[0225]
[0226] (wherein, X independently represents a halogen atom, R a represents a hydroxyalkyl group or a group represented by formula (i).
[0227] In addition, for example, as shown in the following Scheme 2, a triazine ring-containing polymer (27) can be obtained by reacting a triazine compound (29) and an aryl diamino compound (32) in an appropriate organic solvent, and then reacting with at least one aryl amino compound (31) selected from an aryl amino compound having a hydroxyalkyl group and an aryl amino compound having a group represented by formula (i) as a terminal blocking agent.
[0228] Solution 2
[0229]
[0230] (wherein, X independently represents a halogen atom, R a represents a hydroxyalkyl group or a group represented by formula (i).
[0231] In the above scheme 1 or scheme 2, the charging ratio of the aromatic diamino compound (30) or (32) can be arbitrary as long as the target polymer can be obtained, but the aromatic diamino compound (30) or (32) is preferably 0.01 to 10 equivalents, more preferably 0.7 to 5 equivalents, relative to 1 equivalent of the triazine compound (29).
[0232] The aryl diamino compound (30) or (32) may be added in the form of a pure substance or in the form of a solution dissolved in an organic solvent. However, the latter method is preferred in view of ease of handling and ease of reaction control.
[0233] The reaction temperature can be appropriately set within the range from the melting point to the boiling point of the solvent used, and is preferably about -30 to 150°C, more preferably -10 to 100°C.
[0234] As another embodiment, there can be mentioned a method shown in the following embodiment 3. In this method, after a triazine compound (29) and an aryl diamino compound (30) are reacted in a suitable organic solvent, the triazine compound (29) and an aryl diamino compound (30) are reacted with an aryl amino compound (31') having a hydroxyalkyl group as a terminal blocking agent to obtain a triazine ring-containing polymer (23') (first stage), and thereafter, a (meth) acrylate compound having an isocyanate group represented by the formula (i') is further allowed to act on the hydroxyl group of the hydroxyalkyl group contained in the triazine ring-containing polymer (23') (second stage), thereby obtaining a triazine ring-containing polymer (23).
[0235] It should be noted that, when the target product is a triazine ring-containing polymer (23'), the second-stage reaction may not be performed and the first-stage reaction may be completed.
[0236] Solution 3
[0237]
[0238] (Where R a1 represents hydroxyalkyl, X, A 3 , A 4 , R a and a have the same meanings as above. )
[0239] As another embodiment, there can be mentioned a method shown in the following embodiment 4. In this method, after a triazine compound (29) and an aryl diamino compound (32) are reacted in a suitable organic solvent, the triazine ring-containing polymer (27') is obtained by reacting with an aryl amino compound (31') having a hydroxyalkyl group as a terminal blocking agent (first stage), and then a (meth) acrylate compound having an isocyanate group represented by the formula (i') is further allowed to act on the hydroxyl group of the hydroxyalkyl group contained in the triazine ring-containing polymer (27') (second stage), thereby obtaining a triazine ring-containing polymer (27).
[0240] It should be noted that, when the target product is a triazine ring-containing polymer (27'), the second-stage reaction may be omitted and the reaction may be terminated in the first stage.
[0241] Solution 4
[0242]
[0243] (Where R a1 represents hydroxyalkyl, X, A 3 , A 4 , R a and a have the same meanings as above. )
[0244] In the above scheme 3, the charging ratio and addition method of the aryl diamino compound (30) in the first stage, and the reaction temperature in the reaction until the triazine ring-containing polymer (23') is obtained can be the same as those described in scheme 1.
[0245] In the second stage, the charging ratio of the (meth)acrylate compound having an isocyanate group represented by the formula (i') to the triazine ring-containing polymer (23') can be arbitrarily set according to the ratio of the hydroxyalkyl group to the group represented by the formula (i), and is preferably 0.1 to 10 equivalents, more preferably 0.5 to 5 equivalents, further preferably 0.7 to 3 equivalents, and further preferably 0.9 to 1.5 equivalents, relative to 1 equivalent of the aromatic amino compound having a hydroxyalkyl group used. For example, when all the hydroxyalkyl groups contained in the triazine ring-containing polymer (23') are groups represented by the formula (i), the charging ratio of the (meth)acrylate compound is preferably 1.0 to 10 equivalents, more preferably 1.0 to 5 equivalents, further preferably 1.0 to 3 equivalents, and further preferably 1.0 to 1.5 equivalents, relative to 1 equivalent of the aromatic amino compound having a hydroxyalkyl group used.
[0246] The reaction temperature in this reaction is the same as that in the reaction for obtaining the triazine ring-containing polymer (23'), but is preferably 30 to 80°C, more preferably 40 to 70°C, and even more preferably 50 to 60°C in order to prevent the (meth)acryloyl group from being polymerized during the reaction.
[0247] In the above scheme 4, the charging ratio and addition method of the aryl diamino compound (32) in the first stage, and the reaction temperature in the reaction until the triazine ring-containing polymer (27') is obtained can be the same as those described in scheme 2.
[0248] In the second stage, the charging ratio of the (meth)acrylate compound having an isocyanate group represented by the formula (i') to the triazine ring-containing polymer (27') can be arbitrarily set according to the ratio of the hydroxyalkyl group to the group represented by the formula (i), and is preferably 0.1 to 10 equivalents, more preferably 0.1 to 5 equivalents, further preferably 0.1 to 3 equivalents, and further preferably 0.1 to 1.05 equivalents, relative to 1 equivalent of the aromatic amino compound having a hydroxyalkyl group used. For example, when all the hydroxyalkyl groups contained in the triazine ring-containing polymer (22') are groups represented by the formula (i), the charging ratio of the (meth)acrylate compound is preferably 1.0 to 10 equivalents, more preferably 1.0 to 5 equivalents, further preferably 1.0 to 3 equivalents, and further preferably 1.0 to 1.05 equivalents, relative to 1 equivalent of the aromatic amino compound having a hydroxyalkyl group used.
[0249] The reaction temperature in this reaction is the same as the reaction temperature in the reaction for obtaining the triazine ring-containing polymer (27'), but is preferably 30 to 80°C, more preferably 40 to 70°C, and even more preferably 50 to 60°C in order to prevent the (meth)acryloyl group from being polymerized during the reaction.
[0250] In the second stage of Schemes 3 and 4, the reaction may be carried out in the presence of a polymerization inhibitor in order to prevent the (meth)acryloyl group from being polymerized during the reaction.
[0251] Examples of the polymerization inhibitor include N-methyl-N-nitrosoaniline, N-nitrosophenylhydroxylamine or its salts, benzoquinones, phenolic polymerization inhibitors, phenothiazines, etc. Among them, N-nitrosophenylhydroxylamine or its salts are preferred because of their excellent polymerization inhibition effect.
[0252] Examples of the N-nitrosophenylhydroxylamine salts include N-nitrosophenylhydroxylamine ammonium salt and N-nitrosophenylhydroxylamine aluminum salt.
[0253] Examples of the benzoquinones include p-benzoquinone and 2-methyl-1,4-benzoquinone.
[0254] Examples of the phenolic polymerization inhibitor include hydroquinone, p-methoxyphenol, 4-tert-butylcatechol, 2-tert-butylhydroquinone, and 2,6-di-tert-butyl-4-methylphenol.
[0255] The amount of the polymerization inhibitor used is not particularly limited, and may be, for example, 1 to 200 ppm, or 10 to 100 ppm, in terms of mass ratio, relative to the (meth)acrylate compound having an isocyanate group represented by formula (i′).
[0256] By using a polymerization inhibitor, even if the reaction temperature is raised to about 60 to 80° C., the polymerization of the (meth)acryloyl group can be suppressed and the second step reaction can be carried out.
[0257] As the organic solvent, various solvents commonly used in this reaction can be used, for example, tetrahydrofuran (THF), dioxane, dimethyl sulfoxide; N,N-dimethylformamide, N-methyl-2-pyrrolidone, tetramethyl urea, hexamethylphosphoramide, N,N-dimethylacetamide, N-methyl-2-piperidone, N,N-dimethylethylene urea, N,N,N',N'-tetramethylmalonamide, N-methylcaprolactam, N-acetylpyrrolidine, N,N-diethylacetamide, N-ethyl-2-pyrrolidone, N,N-dimethylpropionic acid amide, N,N-dimethylisobutylamide, N-methylformamide, N,N'-dimethylpropylene urea and other amide solvents and mixed solvents thereof.
[0258] Among them, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, N,N-dimethylacetamide and a mixture thereof are preferred, and N,N-dimethylacetamide and N-methyl-2-pyrrolidone are particularly preferred.
[0259] In the first-stage reaction of the above-mentioned scheme 1 or scheme 2, various bases commonly used during or after polymerization may be added.
[0260] Specific examples of the base include potassium carbonate, potassium hydroxide, sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium ethoxide, sodium acetate, lithium carbonate, lithium hydroxide, lithium oxide, potassium acetate, magnesium oxide, calcium oxide, barium hydroxide, trilithium phosphate, trisodium phosphate, tripotassium phosphate, cesium fluoride, aluminum oxide, ammonia, n-propylamine, trimethylamine, triethylamine, diisopropylamine, diisopropylethylamine, N-methylpiperidine, 2,2,6,6-tetramethyl-N-methylpiperidine, pyridine, 4-dimethylaminopyridine, and N-methylmorpholine.
[0261] The amount of the base added is preferably 1 to 100 equivalents, more preferably 1 to 10 equivalents, relative to 1 equivalent of the triazine compound (29). These bases may be used in the form of aqueous solutions.
[0262] It is preferred that no raw material components remain in the obtained polymer, but a part of the raw material may remain unless the effects of the present invention are impaired.
[0263] After completion of the reaction, the product can be easily purified by a reprecipitation method or the like.
[0264] As the end-capping method using the aromatic amino compound having a crosslinking group, a known method may be adopted.
[0265] In this case, the amount of the end-capping agent used is preferably about 0.05 to 10 equivalents, more preferably 0.1 to 5 equivalents, and further preferably 0.5 to 2 equivalents, based on 1 equivalent of the halogen atoms derived from the remaining triazine compound not used in the polymerization reaction.
[0266] The reaction solvent and reaction temperature may be the same as those described in the first step reaction of Scheme 1 or Scheme 2. The end-capping agent may be added simultaneously with the aryldiamino compound (30) or (32).
[0267] It should be noted that an unsubstituted arylamino compound having no crosslinking group may be used and end-capped with two or more groups. Examples of the aryl group of the unsubstituted arylamino compound include the same groups as described above.
[0268] Specific examples of the unsubstituted arylamino group include groups represented by the following formula (33), but are not limited thereto.
[0269]
[0270] In addition, the unsubstituted arylamino group can be introduced using the corresponding unsubstituted arylamino compound in the production method described later.
[0271] Specific examples of the unsubstituted arylamino compound include aniline and the like.
[0272] In addition, when an unsubstituted arylamino group is introduced, from the viewpoint of achieving solubility in an organic solvent and yellowing resistance in a good balance, the ratio of the arylamino compound having a cross-linking group to the unsubstituted arylamino compound is preferably 0.1 to 1.0 mol, more preferably 0.1 to 0.5 mol, and even more preferably 0.1 to 0.3 mol per 1 mol of the arylamino compound having a cross-linking group.
[0273] The triazine ring-containing polymer of the present invention can be preferably used as a film-forming composition. In this case, a crosslinking agent may be added.
[0274] The crosslinking agent is not particularly limited as long as it is a compound having a substituent that can react with the crosslinking group of the triazine ring-containing polymer.
[0275] Examples of such compounds include melamine compounds having a cross-linking substituent such as a methylol group or a methoxymethyl group (e.g., phenolic plastic compounds, aminoplast compounds, etc.), substituted urea compounds, compounds containing a cross-linking substituent such as an epoxy group or an oxetane group (e.g., a polyfunctional epoxy compound, a polyfunctional oxetane compound, etc.), compounds containing a blocked isocyanate group, compounds having an acid anhydride group, compounds having a (meth)acrylic group, and the like. From the viewpoint of heat resistance or storage stability, compounds containing an epoxy group, a blocked isocyanate group, or a (meth)acrylic group are preferred, and compounds having a blocked isocyanate group, or polyfunctional epoxy compounds and / or polyfunctional (meth)acrylic compounds that can provide a composition that can be photocured without using an initiator are particularly preferred.
[0276] It should be noted that when these compounds are used for terminal treatment of polymers, they only need to have at least one substituent that forms a crosslink, and when they are used for crosslinking treatment between polymers, they need to have at least two substituents that form a crosslink.
[0277] The polyfunctional epoxy compound is not particularly limited as long as it has two or more epoxy groups in one molecule.
[0278] Specific examples thereof include tris(2,3-epoxypropyl)isocyanurate, 1,4-butanediol diglycidyl ether, 1,2-epoxy-4-(epoxyethyl)cyclohexane, glycerol triglycidyl ether, diethylene glycol diglycidyl ether, 2,6-diglycidylphenyl glycidyl ether, 1,1,3-tri[p-(2,3-epoxypropyloxy)phenyl]propane, 1,2-cyclohexanedicarboxylic acid diglycidyl ester, 4,4'-methylenebis(N,N-diglycidylaniline), 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, trimethylolethane triglycidyl ether, bisphenol-A-diglycidyl ether, and pentaerythritol polyglycidyl ether.
[0279] In addition, as commercially available products, YH-434 and YH434L (manufactured by Nippon Steel Chemical Materials Co., Ltd.) as epoxy resins having at least two epoxy groups; EPOLEAD GT-401, EPOLEAD GT-403, EPOLEAD GT-301, EPOLEAD GT-302, and CELLOXIDE 100 as epoxy resins having a cyclohexene oxide structure can be used. 2021, CELLOXIDE3000 (manufactured by Daicel Corporation); jER1001, jER1002, jER1003, jER1004, jER1007, jER1009, jER1010, jER828 (manufactured by Mitsubishi Chemical Corporation) as bisphenol A type epoxy resin; jER807 (manufactured by Mitsubishi Chemical Corporation) as bisphenol F type epoxy resin; jER152, jER154 (manufactured by Mitsubishi Chemical Corporation) as phenol novolac type epoxy resin, EPPN 201, EPPN 202 (above, manufactured by Nippon Kayaku Co., Ltd.); EOCN-102, EOCN-103S, EOCN-104S, EOCN-1020, EOCN-1025, EOCN-1027 (above, manufactured by Nippon Kayaku Co., Ltd.), jER180S75 (manufactured by Mitsubishi Chemical Corporation) as resol novolac type epoxy resins; DENACOLEX-252 (manufactured by Nagase ChemteX Co., Ltd.), CY175, CY177, CY179 (above, manufactured by CIBA-GEIGY AG), Araldite CY-182, Araldite CY-192, Araldite CY-184 (above, manufactured by CIBA-GEIGY AG), EPICLON 200, EPICLON 400 (above, manufactured by DIC Corporation), jER871, jER 872 (manufactured by Mitsubishi Chemical Corporation), ED-5661, ED-5662 (manufactured by Celanese Coatings Co., Ltd.); aliphatic polyglycidyl ethers such as DENACOL EX-611, DENACOL EX-612, DENACOL EX-614, DENACOL EX-622, DENACOL EX-411, DENACOL EX-512, DENACOL EX-522, DENACOL EX-421, DENACOL EX-313, DENACOL EX-314, DENACOL EX-321 (manufactured by Nagase ChemteX Co., Ltd.), etc.
[0280] The polyfunctional (meth)acrylic compound is not particularly limited as long as it has two or more (meth)acrylic groups in one molecule.
[0281] Specific examples thereof include ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, ethoxylated glycerol triacrylate, ethoxylated glycerol trimethacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetramethacrylate, ethoxylated dipentaerythritol hexaacrylate, polyglycerol monoethylene oxide polyacrylate, Ester, polyglycerol polyethylene glycol polyacrylate, dipentaerythritol hexaacrylate, dipentaerythritol hexamethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, polyacid-modified acrylic oligomers, etc.
[0282] In addition, the polyfunctional (meth)acrylic compound can be obtained as a commercial product. Specific examples thereof include NK ester A-200, NK ester A-400, NK ester A-600, NK ester A-1000, NK ester A-9300 (tris (2-acryloyloxyethyl) isocyanurate), NK ester A-9300-1CL, NK ester A-TMPT, NK ester UA-53H, NK ester 1G, NK ester 2G, NK ester 3G, NK ester 4G, NK ester 9G, NK ester 14G, NK ester 23G, NK ester ABE-300, NK ester A-BPE-4, NK ester A-BPE-6, NK ester A-BPE-10, NK ester A-BPE-20, N K ester A-BPE-30, NK ester BPE-80N, NK ester BPE-100N, NK ester BPE-200, NK ester BPE-500, NK ester BPE-900, NK ester BPE-1300N, NK ester A-GLY-3E, NK ester A-GLY-9E, NK ester A-GLY-20E, NK ester A-TMPT-3EO, NK ester A-TMPT-9EO, NK ester AT-20E, NK ester ATM-4E, NK ester ATM-35E, APG-100, APG-200 (all manufactured by Shin-Nakamura Chemical Co., Ltd.), KAYARAD (registered trademark) DPEA-12, KAYARAD PEG400DA, KAYARAD THE-330, KAYARAD RP-1040 (all manufactured by Nippon Kayaku Co., Ltd.), Aronix M-210, M-350 (all manufactured by Toagosei Co., Ltd.), KAYARAD (registered trademark) DPHA, KAYARAD NPGDA, KAYARAD PET30 (all manufactured by Nippon Kayaku Co., Ltd.), NK Ester A-DPH, NK Ester A-TMPT, NK Ester A-DCP, NK Ester A-HD-N, NK Ester TMPT, NK Ester DCP, NK Ester NPG, NK Ester HD-N (all manufactured by Shin-Nakamura Chemical Co., Ltd.), NK OLIGO U-15HA (all manufactured by Shin-Nakamura Chemical Co., Ltd.), NK polymer Vanaresin GH-1203 (all manufactured by Shin-Nakamura Chemical Co., Ltd.), DN-0075 (all manufactured by Nippon Kayaku Co., Ltd.), and the like.
[0283] The polyacid-modified acrylic oligomer is also available as a commercial item, and specific examples thereof include Aronix M-510 and 520 (each manufactured by Toagosei Co., Ltd.).
[0284] The compound having an acid anhydride group is not particularly limited as long as it is a carboxylic anhydride formed by dehydration condensation of two molecules of carboxylic acid. Specific examples thereof include compounds having one acid anhydride group in the molecule, such as phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, nadic anhydride, methylnadic anhydride, maleic anhydride, succinic anhydride, octyl succinic anhydride, and dodecenyl succinic anhydride; 1,2,3,4-cyclobutanetetracarboxylic anhydride, pyromellitic anhydride, 3,4-dicarboxy-1,2,3,4- Compounds having two anhydride groups in the molecule, such as tetrahydro-1-naphthalene succinic dianhydride, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydro-3-furyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, and 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, etc.
[0285] The compound containing a blocked isocyanate group is not particularly limited as long as it has two or more isocyanate groups (-NCO) blocked with a suitable protective group in one molecule, and when exposed to a high temperature during thermal curing, the protective group (blocking portion) is thermally dissociated and removed, and a cross-linking reaction occurs between the generated isocyanate group and the cross-linking group (for example, a hydroxyl group) of the triazine ring-containing polymer of the present invention. For example, there can be mentioned a compound having two or more groups represented by the following formula in one molecule (it should be noted that these groups may be the same or different).
[0286]
[0287] (Where R b represents an end-capping organic group. )
[0288] Such a compound can be obtained, for example, by reacting a compound having two or more isocyanate groups in one molecule with an appropriate blocking agent.
[0289] Examples of the compound having two or more isocyanate groups in one molecule include isophorone diisocyanate, 1,6-hexamethylene diisocyanate, methylenebis(4-cyclohexyl isocyanate), polyisocyanates of trimethylhexamethylene diisocyanate, dimers and trimers thereof, and reaction products of these with diols, triols, diamines or triamines.
[0290] As the end-capping agent, for example, there can be mentioned alcohols such as methanol, ethanol, isopropanol, n-butanol, 2-ethoxyhexanol, 2-N,N-dimethylaminoethanol, 2-ethoxyethanol, and cyclohexanol; phenols such as phenol, o-nitrophenol, p-chlorophenol, o-cresol, m-cresol, or p-cresol; lactams such as ε-caprolactam, oximes such as acetone oxime, methyl ethyl ketone oxime, methyl isobutyl ketone oxime, cyclohexanone oxime, acetophenone oxime, and benzophenone oxime; pyrazoles such as pyrazole, 3,5-dimethylpyrazole, and 3-methylpyrazole; thiols such as dodecyl mercaptan and benzene mercaptan, and the like.
[0291] The blocked isocyanate group-containing compound can also be obtained as a commercial product. Specific examples thereof include TAKENATE (registered trademark) B-830, B-815N, B-842N, B-870N, B-874N, B-882N, B-7005, B-7030, B-7075, B-5010 (all manufactured by Mitsui Chemicals, Inc.), Duranate (registered trademark) 17B-60PX, Duranate TPA-B80E, Duranate MF-B60X, Duranate MF-K60X, Duranate E402-B80T (all manufactured by Asahi Kasei Corporation), Karenz MOI-BM (registered trademark) (all manufactured by Showa Denko K.K.), TRIXENE (registered trademark) BI-7950, BI-7951, BI-7960, BI-7961, BI-7963, BI-7982, BI-7991, BI-7992 (manufactured by Baxendenchemicals LTD), and the like.
[0292] The aminoplast compound is not particularly limited as long as it has two or more methoxymethyl groups in one molecule, and examples thereof include CYMEL series compounds such as hexamethoxymethylmelamine CYMEL (registered trademark) 303, tetrabutoxymethyl glycoluril CYMEL 1170, and tetramethoxymethylbenzoguanamine CYMEL 1123 (all manufactured by Nippon Cytec Industries Co., Ltd.); methylated melamine resins such as NIKALAC (registered trademark) MW-30HM, NIKALAC MW-390, NIKALAC MW-100LM, and NIKALAC MX-750LM; and methylated urea resins such as NIKALAC series compounds such as NIKALAC MX-270, NIKALAC MX-280, and NIKALAC MX-290 (all manufactured by Sanwa Chemical Co., Ltd.).
[0293] The polyfunctional oxetane compound is not particularly limited as long as it has two or more oxetane groups in one molecule, and examples thereof include oxetane group-containing OXT-221, OX-SQ-H, and OX-SC (all manufactured by Toagosei Co., Ltd.).
[0294] The phenolic plastic compound has two or more hydroxymethyl groups in one molecule, and when exposed to high temperatures during thermal curing, cross-linking reaction occurs with the cross-linking groups of the triazine ring-containing polymer of the present invention through a dehydration condensation reaction.
[0295] Examples of the phenolic plastic compound include 2,6-dihydroxymethyl-4-methylphenol, 2,4-dihydroxymethyl-6-methylphenol, bis(2-hydroxy-3-hydroxymethyl-5-methylphenyl)methane, bis(4-hydroxy-3-hydroxymethyl-5-methylphenyl)methane, 2,2-bis(4-hydroxy-3,5-dihydroxymethylphenyl)propane, bis(3-formyl-4-hydroxyphenyl)methane, bis(4-hydroxy-2,5-dimethylphenyl)formylmethane, and α,α-bis(4-hydroxy-2,5-dimethylphenyl)-4-formyltoluene.
[0296] Bakelite compounds can also be obtained as commercial products. Specific examples thereof include 26DMPC, 46DMOC, DM-BIPC-F, DM-BIOC-F, TM-BIP-A, BISA-F, BI25X-DF, and BI25X-TPA (all manufactured by Asahi Organic Materials Industries, Ltd.).
[0297] Among them, polyfunctional (meth)acrylic compounds are preferred from the viewpoint of being able to suppress the decrease in refractive index due to the addition of a crosslinking agent and to rapidly carry out the curing reaction. Among them, polyfunctional (meth)acrylic compounds having the following isocyanuric acid skeleton are more preferred because of their excellent compatibility with triazine ring-containing polymers.
[0298] Examples of the polyfunctional (meth)acrylic compound having such a skeleton include NK ester A-9300 and NK ester A-9300-1CL (both manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0299]
[0300] (Where R 111 ~R 113 are independently monovalent organic groups having at least one (meth)acrylic group at the end.
[0301] In addition, from the viewpoint of further increasing the curing speed and improving the solvent resistance, acid resistance and alkali resistance of the obtained cured film, it is preferred to use a polyfunctional (meth) acrylic compound (hereinafter referred to as a low-viscosity cross-linking agent) which is liquid at 25°C and has a viscosity of 5000 mPa·s or less, preferably 1 to 3000 mPa·s, more preferably 1 to 1000 mPa·s, and further preferably 1 to 500 mPa·s, alone or in combination of two or more, or in combination with the above-mentioned polyfunctional (meth) acrylic compound having an isocyanuric acid skeleton.
[0302] Such low-viscosity crosslinking agents are also commercially available, and examples thereof include crosslinking agents having relatively long chain lengths between (meth)acrylic groups such as NK ester A-GLY-3E (85 mPa·s, 25°C), NK ester A-GLY-9E (95 mPa·s, 25°C), NK ester A-GLY-20E (200 mPa·s, 25°C), NK ester A-TMPT-3EO (60 mPa·s, 25°C), NK ester A-TMPT-9EO, NK ester ATM-4E (150 mPa·s, 25°C), and NK ester ATM-35E (350 mPa·s, 25°C) (all manufactured by Shin-Nakamura Chemical Co., Ltd.) among the above-mentioned polyfunctional (meth)acrylic compounds.
[0303] In addition, considering that the alkali resistance of the obtained cured film is also improved, it is preferred to use at least one of NK ester A-GLY-20E (manufactured by Shin-Nakamura Chemical Co., Ltd.) and NK ester ATM-35E (manufactured by Shin-Nakamura Chemical Co., Ltd.) in combination with the above-mentioned polyfunctional (meth) acrylic compound having an isocyanuric acid skeleton.
[0304] In addition, when a thin film composed of the triazine ring-containing polymer of the present invention is laminated on a protective film such as a PET or polyolefin film and light irradiated through the protective film, good curability can be obtained without being hindered by oxygen even in the thin film laminate. In this case, since the protective film needs to be peeled off after curing, it is preferable to use a polyacid-modified acrylic oligomer that provides a thin film with good peelability.
[0305] The crosslinking agent may be used alone or in combination of two or more. The amount of the crosslinking agent used is preferably 1 to 100 parts by mass relative to 100 parts by mass of the triazine ring-containing polymer, and in consideration of solvent resistance, the lower limit is preferably 2 parts by mass, more preferably 5 parts by mass, and in consideration of refractive index control, the upper limit is preferably 20 parts by mass, more preferably 15 parts by mass.
[0306] In the composition of the present invention, an initiator can be added according to each crosslinking agent. It should be noted that, as described above, when a multifunctional epoxy compound and / or a multifunctional (meth) acrylic compound is used as a crosslinking agent, photocuring is performed without using an initiator to obtain a cured film, but in this case, it is not harmful to use an initiator.
[0307] When a polyfunctional epoxy compound is used as a crosslinking agent, a photoacid generator or a photobase generator can be used.
[0308] As the photoacid generator, any one appropriately selected from known ones may be used. For example, an onium salt derivative such as a diazonium salt, a sulfonium salt, or an iodonium salt can be used.
[0309] Specific examples thereof include aryl diazonium salts such as phenyldiazonium hexafluorophosphate, 4-methoxyphenyldiazonium hexafluoroantimonate, and 4-methylphenyldiazonium hexafluorophosphate; diaryl iodonium salts such as diphenyliodonium hexafluoroantimonate, di(4-methylphenyl)iodonium hexafluorophosphate, and di(4-tert-butylphenyl)iodonium hexafluorophosphate; triphenylsulfonium hexafluoroantimonate, tri(4-methoxyphenyl)sulfonium hexafluorophosphate, diphenyl-4-thiophenoxyphenylsulfonium hexafluoroantimonate, diphenyl-4-thiophenoxyphenylsulfonium hexafluorophosphate, 4,4'- Triarylsulfonium salts such as bis(diphenylsulfonyl)phenylene sulfide-bishexafluoroantimonate, 4,4'-bis(diphenylsulfonyl)phenylene sulfide-bishexafluorophosphate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]phenylene sulfide-bishexafluoroantimonate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]phenylene sulfide-bis-hexafluorophosphate, 4-[4'-(benzoyl)phenylthio]phenyl-bis(4-fluorophenyl)sulfonium hexafluoroantimonate, and 4-[4'-(benzoyl)phenylthio]phenyl-bis(4-fluorophenyl)sulfonium hexafluorophosphate.
[0310] These onium salts can be commercially available products. Specific examples thereof include SAN-AID SI-60, SI-80, SI-100, SI-60L, SI-80L, SI-100L, SI-L145, SI-L150, SI-L160, SI-L110, and SI-L147 (all manufactured by Sanshin Chemical Industry Co., Ltd.), UVI-6950, UVI-6970, UVI-6974, UVI-6990, and UVI-6992 (all manufactured by Union Carbide Corporation), CPI-100P, CPI-100A, CPI-200K, and CPI-200S (all manufactured by San-Apro Co., Ltd.), Adeka Optomer SP-150, SP-151, SP-170, and SP-171 (all manufactured by Asahi Denka Kogyo Co., Ltd.), Irgacure 261 (manufactured by BASF), CI-2481, CI-2624, CI-2639, CI-2064 (manufactured by Nippon Soda Co., Ltd.), CD-1010, CD-1011, CD-1012 (manufactured by Sartomer Co., Ltd.), DS-100, DS-101, DAM-101, DAM-102, DAM-105, DAM-201, DSM-301, NAI-100, NAI-101, NAI-105, NAI-106, SI-100, SI-101, SI-105, SI-106, PI-105, NDI-105, BENZOIN TOSYLATE, MBZ-101, MBZ-301, PYR-100, PYR-200, DNB-101, NB-101, NB-201, BBI-101, BBI-102, BBI-103, BBI-1 09 (above, manufactured by Midori Chemical Co., Ltd.), PCI-061T, PCI-062T, PCI-020T, PCI-022T (above, manufactured by Nippon Kayaku Co., Ltd.), IBPF, IBCF (manufactured by Sanwa Chemical Co., Ltd.), etc.
[0311] On the other hand, the photobase generator may be appropriately selected from known photobase generators and used. For example, cobalt amine complex-based, oxime carboxylate-based, carbamate-based, and quaternary ammonium salt-based photobase generators may be used.
[0312] Specific examples thereof include 2-nitrobenzylcyclohexylcarbamate, triphenylmethanol, O-carbamoylhydroxyamide, O-carbamoyloxime, [[(2,6-dinitrobenzyl)oxy]carbonyl]cyclohexylamine, bis[[(2-nitrobenzyl)oxy]carbonyl]hexane 1,6-diamine, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, (4-morpholinobenzoyl)-1-benzyl-1-dimethylamine, propane, N-(2-nitrobenzyloxycarbonyl)pyrrolidine, hexaamminecobalt(III) tris(triphenylmethylborate), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 2,6-dimethyl-3,5-diacetyl-4-(2'-nitrophenyl)-1,4-dihydropyridine, 2,6-dimethyl-3,5-diacetyl-4-(2',4'-dinitrophenyl)-1,4-dihydropyridine, etc.
[0313] As the photobase generator, a commercially available product may be used, and specific examples thereof include TPS-OH, NBC-101, and ANC-101 (all product names, manufactured by Midori Chemical Co., Ltd.).
[0314] When a photoacid or photobase generator is used, it is preferably used in an amount within a range of 0.1 to 15 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the polyfunctional epoxy compound.
[0315] In addition, the epoxy resin curing agent can be mix|blended in the amount of 1-100 mass parts with respect to 100 mass parts of polyfunctional epoxy compounds as needed.
[0316] On the other hand, when a polyfunctional (meth)acrylic compound is used, a photoradical polymerization initiator can be used.
[0317] The photoradical polymerization initiator may be appropriately selected from known ones and used. Examples thereof include acetophenones, benzophenones, Michler's benzoyl benzoate, amyl oxime ester, oxime esters, tetramethylthiuram monosulfide, and thioxanthones.
[0318] In particular, photo-cleavage type photo-radical polymerization initiators are preferred. Photo-cleavage type photo-radical polymerization initiators are described in Latest UV Curing Technology (page 159, publisher: Kazuhiro Takahashi, Publisher: Technical Information Association Co., Ltd., published in 1991).
[0319] Examples of commercially available photoradical polymerization initiators include Irgacure 127, 184, 369, 379, 379EG, 651, 500, 754, 819, 903, 907, 784, 2959, CGI1700, CGI1750, CGI1850, CG24-61, OXE01, OXE02, Darocur 1116, 1173, and MBF manufactured by BASF, Lucirin TPO manufactured by BASF, Yubekuriru P36 manufactured by UCB, and Esacure KIP150, KIP65LT, KIP100F, KT37, KT55, KTO46, and KIP75 / B manufactured by Fratelli Lamberti.
[0320] When using a photoradical polymerization initiator, it is preferably used in an amount within a range of 0.1 to 200 parts by mass, more preferably 1 to 150 parts by mass, based on 100 parts by mass of the polyfunctional (meth)acrylate compound.
[0321] Furthermore, in the composition of the present invention, a polyfunctional thiol compound having two or more mercapto groups in the molecule may be added for the purpose of promoting the reaction between the triazine ring-containing polymer and the crosslinking agent.
[0322] Specifically, a polyfunctional thiol compound represented by the following formula is preferred.
[0323]
[0324] The above-mentioned L represents a divalent to tetravalent organic group, preferably a divalent to tetravalent aliphatic group having 2 to 12 carbon atoms or a divalent to tetravalent heterocyclic ring-containing group, and more preferably a divalent to tetravalent aliphatic group having 2 to 8 carbon atoms or a trivalent group having an isocyanuric acid skeleton (1,3,5-triazine-2,4,6(1H,3H,5H)-trione ring) represented by the following formula.
[0325] The above n represents an integer of 2 to 4 corresponding to the valence of L.
[0326]
[0327] (In the formula, "·" represents a bonding portion with an oxygen atom.)
[0328] Specific examples of the compound include 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, pentaerythritol tetrakis(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), and trimethylolethane tris(3-mercaptobutyrate).
[0329] These polyfunctional thiol compounds are commercially available, and examples thereof include Karenz MT-BD1, Karenz MT NR1, Karenz MT PE1, TPMB, and TEMB (all manufactured by Showa Denko K.K.).
[0330] These polyfunctional thiol compounds may be used alone or in combination of two or more.
[0331] When a polyfunctional thiol compound is used, the amount thereof added is not particularly limited unless it has an adverse effect on the obtained thin film, but in the present invention, it is preferably 0.01 to 10% by mass, more preferably 0.03 to 6% by mass, based on 100% by mass of the solid content.
[0332] It is preferred to add various solvents to the composition of the present invention so as to dissolve the triazine ring-containing polymer before use.
[0333] Examples of the solvent include water, toluene, p-xylene, o-xylene, m-xylene, ethylbenzene, styrene, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol methyl ether acetate, propylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol monoisopropyl ether, ethylene glycol methyl ether acetate, propylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol monoisopropyl ether, ethylene glycol methyl ether acetate, propylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol monoisopropyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, ethylene glycol mono ... diethyl alcohol, dipropylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol dimethyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol, 1-octanol, ethylene glycol, hexanediol, trimethyl glycol, 1-methoxy-2-butanol, cyclohexanol, diacetone alcohol, furfuryl alcohol, tetrahydrofurfuryl alcohol, propylene glycol, benzyl alcohol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol diol, γ-butyrolactone, acetone, methyl ethyl ketone, methyl isopropyl ketone, diethyl ketone, methyl isobutyl ketone, methyl n-butyl ketone, cyclopentanone, cyclohexanone, ethyl acetate, isopropyl acetate, n-propyl acetate, isobutyl acetate, n-butyl acetate, ethyl lactate, methanol, ethanol, isopropyl alcohol, tert-butyl alcohol, allyl alcohol, n-propyl alcohol, 2-methyl-2-butanol, isobutyl alcohol, n-butanol, 2-methyl-1-butanol, 1-pentanol, 2-methyl-1-pentanol, 2-ethylhexanol, 1-methoxy-2-propanol, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, dimethyl sulfoxide, N-cyclohexyl-2-pyrrolidone, etc., and these may be used alone or in combination of two or more.
[0334] As described above, since the triazine ring-containing polymer of the present invention has excellent solubility in organic solvents, it dissolves well in glycol ester solvents such as ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, diethylene glycol monobutyl ether acetate, and diethylene glycol monoethyl ether acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclopentanone, cyclohexanone, and diacetone alcohol; and ester solvents such as ethyl acetate, methyl acetate, butyl acetate, methoxybutyl acetate, cellosolve acetate, amyl acetate, n-propyl acetate, isopropyl acetate, methyl lactate, ethyl lactate, and butyl lactate. Therefore, it is particularly suitable for forming a thin film on a portion where these solvents are required.
[0335] At this time, the solid content concentration in the composition is not particularly limited as long as it does not affect the storage stability, and can be appropriately set according to the thickness of the target film. Specifically, from the viewpoint of solubility and storage stability, the solid content concentration is preferably 0.1 to 50% by mass, and more preferably 0.1 to 40% by mass.
[0336] The composition of the present invention may contain other components besides the triazine ring-containing polymer, the crosslinking agent and the solvent, such as additives such as a leveling agent, a surfactant and a silane coupling agent, as long as the effects of the present invention are not impaired.
[0337] Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl allyl ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; polyoxyethylene-polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate; nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate; and EFtop® (trade name). EF301, EF303, EF352 (manufactured by Mitsubishi Materials Electronics Co., Ltd. (formerly manufactured by Gemco Co., Ltd.)), trade names MEGAFACE F171, F173, R-08, R-30, R-40, F-553, F-554, RS-75, RS-72-K (manufactured by DIC Corporation), FLUORAD FC430, FC431 (manufactured by Sumitomo 3M Co., Ltd.), brand name AsahiGuard AG710, Surflon Fluorine-based surfactants such as S-382, SC101, SC102, SC103, SC104, SC105, SC106 (manufactured by AGC Corporation), organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.), BYK-302, BYK-307, BYK-322, BYK-323, BYK-330, BYK-333, BYK-370, BYK-375, BYK-378 (manufactured by BYK-Chemie (Japan) Co., Ltd.), etc.
[0338] These surfactants may be used alone or in combination of two or more. The amount of the surfactant used is preferably 0.0001 to 5 parts by mass, more preferably 0.001 to 1 part by mass, and even more preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the triazine ring-containing polymer.
[0339] After applying the film-forming composition of the present invention onto a substrate, the substrate may be heated to evaporate the solvent as necessary, and then heated or irradiated with light to obtain a desired cured film.
[0340] The composition can be applied by any method, for example, spin coating, dip coating, flow coating, inkjet, jet dispenser, spray coating, rod coating, gravure coating, slit coating, roller coating, transfer printing, brushing, blade coating, air knife coating, or the like.
[0341] In addition, as the substrate, there can be cited substrates composed of silicon, glass forming an indium tin oxide (ITO) film, glass forming an indium zinc oxide (IZO) film, metal nanowires, polyethylene terephthalate (PET), plastic, glass, quartz, ceramics, etc., and flexible substrates with flexibility can also be used.
[0342] The calcination temperature is not particularly limited in order to evaporate the solvent, and can be performed at, for example, 110 to 400°C.
[0343] The firing method is not particularly limited, and for example, evaporation can be performed using a hot plate or an oven in an appropriate environment such as air, an inert gas such as nitrogen, or a vacuum.
[0344] The firing temperature and firing time may be selected to be conditions suitable for the process steps of the target electronic device, and the firing conditions may be selected so that the physical property values of the obtained film are suitable for the required characteristics of the electronic device.
[0345] The conditions for light irradiation are not particularly limited, and appropriate irradiation energy and time may be used depending on the triazine ring-containing polymer and crosslinking agent used.
[0346] The thin film or cured film of the present invention obtained as described above can achieve high heat resistance, high refractive index and low volume shrinkage, and can therefore be used in the field of electronic devices or optical materials such as a component for producing liquid crystal displays, organic EL elements (organic EL displays or organic EL lighting), touch panels, optical semiconductor (LED) elements, solid-state imaging elements, organic thin film solar cells, dye-sensitized solar cells, organic thin film transistors (TFTs), lenses, prism cameras, binoculars, microscopes, semiconductor exposure devices, etc.
[0347] In particular, since the thin film or cured film made from the composition of the present invention has high transparency and high refractive index, when used as a flattening film or light scattering layer for organic EL lighting, its light extraction efficiency (light diffusion efficiency) can be improved and its durability can be improved.
[0348] It should be noted that, when the composition of the present invention is used for the light scattering layer of organic EL lighting, known light diffusing agents can be used as light diffusing agents, without particular limitation. These can be used separately, two or more of the same kind can be used in combination, or two or more of different kinds can be used in combination.
[0349] As a light diffusing agent, an organic light diffusing agent is mentioned, for example.
[0350] Examples of the organic light diffuser include cross-linked polymethyl methacrylate (PMMA) particles, cross-linked polymethyl acrylate particles, cross-linked polystyrene particles, cross-linked styrene acrylic copolymer particles, melamine-formaldehyde particles, silicone resin particles, silica-acrylic composite particles, nylon particles, benzoguanamine-formaldehyde particles, benzoguanamine-melamine-formaldehyde particles, fluororesin particles, epoxy resin particles, polyphenylene sulfide resin particles, polyethersulfone resin particles, polyacrylonitrile particles, and polyurethane particles.
[0351] These light diffusing agents may be those surface-treated with an appropriate surface modifying agent.
[0352] Example
[0353] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that the respective measuring devices used in the Examples are as follows.
[0354] [ 1 H-NMR]
[0355] Apparatus: Bruker NMR System AVANCE III HD 500 (500 MHz).
[0356] Assay solvent: DMSO-d6.
[0357] Reference substance: tetramethylsilane (TMS) (δ 0.0 ppm).
[0358] [GPC]
[0359] Device: HLC-8200GPC manufactured by Tosoh Corporation.
[0360] Column: Tosoh TSKgelα-3000 + Tosoh TSKgelα-4000.
[0361] Column temperature: 40℃.
[0362] Solvent: dimethylformamide (DMF).
[0363] Detector: UV (271 nm).
[0364] Calibration curve: polystyrene standards.
[0365] [Ellipsometer]
[0366] Apparatus: Multi-incident-angle spectroscopic ellipsometer VASE manufactured by JA Woollam (Japan).
[0367] [Spectrophotometer]
[0368] Device: CM-3700A manufactured by Konica Minolta.
[0369] [Optical microscope]
[0370] Apparatus: OLYMPUS BX51 manufactured by Olympus Optical Co., Ltd.
[0371] [UV-Vis-NIR Spectrophotometer]
[0372] Device: V-670 manufactured by JASCO Corporation.
[0373] [1] Synthesis of polymers containing triazine rings
[0374] [Example 1-1] Synthesis of polymer compound [4]
[0375]
[0376] 1,3-phenylenediamine [2] (35.18 g, 0.325 mol, manufactured by Amino-Chem) and 666.3 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.) were added to a 1000 mL four-necked flask, and after nitrogen substitution, the 1,3-phenylenediamine [2] was dissolved in DMAc by stirring. Thereafter, the flask was cooled to -10°C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine [1] (60.0 g, 0.325 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added while confirming that the internal temperature did not exceed 0°C. After stirring for 30 minutes, the oil bath was set to 90 to 100°C, and the reaction solution was heated to an internal temperature of 85°C ± 5°C. After stirring at an internal temperature of 85°C for 1 hour, 2-(4-aminophenyl)ethanol [3] (53.56 g, 0.456 mol, manufactured by Oakwood) was preliminarily dissolved in 107.12 g of DMAc and then added dropwise, and stirred for 3 hours. Thereafter, 2-aminoethanol (59.62 g, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and the mixture was cooled to room temperature and stirred for 30 minutes, after which stirring was stopped. THF (491 g), ammonium acetate (442 g) and ion-exchanged water (442 g) were added to the reaction solution, and stirred for 30 minutes. After stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was recovered. The recovered organic layer was added dropwise to a mixed solution of methanol (491 g) and ion-exchanged water (1964 g) to cause reprecipitation. The obtained precipitate was separated by filtration and dried at 120°C for 8 hours using a reduced pressure dryer to obtain 78.5 g of the target polymer compound [4] (hereinafter referred to as P-1). 1The results of H-NMR spectrum measurement are shown in Figure 1 .
[0377] The weight average molecular weight Mw of compound P-1 measured by GPC in terms of polystyrene was 6070, and the polydispersity Mw / Mn was 2.6.
[0378] [Example 1-2] Synthesis of polymer compound [5]
[0379]
[0380] In a 150 mL four-necked flask, add 25.0 g of the compound P-1 synthesized in Example 1-1, 100.0 g of THF (manufactured by Junsei Chemical Co., Ltd.), and 11.66 g of pure water. After nitrogen substitution, stir to dissolve P-1 in THF. Thereafter, raise the temperature to 60°C, add 12.70 g of 2-isocyanatoethyl acrylate (Karenz AOI, manufactured by Showa Denko K.K.) and stir for 3 hours. Thereafter, cool to room temperature, and add dropwise the reaction solution to a mixture of methanol (149 g) and ion exchange water (448 g) to reprecipitate. The obtained precipitate is separated by filtration and dried at 80°C for 3 hours using a reduced pressure dryer to obtain 21.6 g of the target polymer compound [5] (hereinafter referred to as P-2). 1 The results of H-NMR spectrum measurement are shown in Figure 2 .
[0381] The weight average molecular weight Mw of compound P-2 measured by GPC in terms of polystyrene was 6250, and the polydispersity Mw / Mn was 3.3.
[0382] [Example 1-3] Synthesis of polymer compound [7]
[0383]
[0384] 1,3-phenylenediamine [2] (11.73 g, 0.108 mol, manufactured by Anno Chemical Co., Ltd.) and 204.96 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.) were added to a 500 mL four-necked flask, and after nitrogen substitution, the 1,3-phenylenediamine [2] was dissolved in DMAc by stirring. Thereafter, the flask was cooled to -10°C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine [1] (20.00 g, 0.108 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added while confirming that the internal temperature did not exceed 0°C. After stirring for 30 minutes, 87.8 g of DMAc was added to a 500 mL four-necked flask in advance, and after nitrogen substitution, the oil bath was set to 90 to 100°C so that the internal temperature was 85°C ± 5°C, and the reaction solution was added dropwise. After stirring at an internal temperature of 85°C for 1 hour, aniline [6] (10.10 g, 0.108 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) and 2-(4-aminophenyl)ethanol [3] (104.14 g, 0.759 mol, manufactured by Sugai Chemical Industry Co., Ltd.) previously dissolved in 208.29 g of DMAc were added dropwise, and stirred for 3 hours. After 3 hours, acryloyl chloride (14.72 g, 0.163 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and further stirred for 30 minutes. Thereafter, the temperature was lowered to 60°C, triethylamine (54.87 g, 0.542 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and stirring was stopped for 30 minutes. The reaction solution was mixed with ion exchange water (188.6 g) and THF (210 g) to which 188.6 g of ammonium acetate had been added, which had been prepared in advance, and stirred for 30 minutes. After the stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was recovered. The recovered organic layer was added dropwise to a mixture of methanol (251 g) and ion exchange water (629 g) to reprecipitate. The obtained precipitate was separated by filtration and dried at 120°C for 8 hours using a reduced pressure dryer to obtain 31.0 g of the target polymer compound [7] (hereinafter referred to as P-3). 1 The results of H-NMR spectrum measurement are shown in Figure 3 .
[0385] The weight average molecular weight Mw of compound P-3 measured by GPC in terms of polystyrene was 7270, and the polydispersity Mw / Mn was 3.3.
[0386] [Comparative Example 1-1] Synthesis of polymer compound [8]
[0387] According to the synthesis method described in International Publication No. 2010 / 128661, a polymer compound [8] (hereinafter referred to as P-4) was synthesized.
[0388]
[0389] Compound P-4 1 The results of H-NMR spectrum measurement are shown in Figure 4 .
[0390] The weight average molecular weight Mw of compound P-4 measured by GPC in terms of polystyrene was 11580, and the polydispersity Mw / Mn was 3.7.
[0391] [Comparative Example 1-2] Synthesis of polymer compound [9]
[0392] According to the synthesis method described in International Publication No. 2013 / 094663, a polymer compound [9] (hereinafter referred to as P-5) was synthesized.
[0393]
[0394] Compound P-5 1 The results of H-NMR spectrum measurement are shown in Figure 5 .
[0395] The weight average molecular weight Mw of compound P-5 measured by GPC in terms of polystyrene was 6182, and the polydispersity Mw / Mn was 5.8.
[0396] [Example 1-4] Synthesis of polymer compound
[10]
[0397]
[0398] 1,3-phenylenediamine [2] (42.22 g, 0.390 mol, manufactured by Anno Chemical Co., Ltd.) and 672.62 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.) were added to a 1000 mL four-necked flask, and after nitrogen substitution, the 1,3-phenylenediamine [2] was dissolved in DMAc by stirring. Thereafter, the flask was cooled to -10°C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine [1] (60.00 g, 0.325 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added while confirming that the internal temperature did not exceed 0°C. After stirring for 30 minutes, the oil bath was set to 90 to 100°C, and the reaction solution was heated to an internal temperature of 85°C ± 5°C. After stirring at an internal temperature of 85°C for 1 hour, aniline [6] (18.18 g, 0.195 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) and 2-(4-aminophenyl)ethanol [3] (26.78 g, 0.195 mol, manufactured by Oakwood Co., Ltd.) preliminarily dissolved in 42.93 g of DMAc were added dropwise, and stirred for 3 hours. Thereafter, 2-aminoethanol (59.62 g, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and the mixture was cooled to room temperature and stirred for 30 minutes, after which stirring was stopped. THF (369 g), ammonium acetate (415 g) and ion-exchanged water (415 g) were added to the reaction solution, and stirred for 30 minutes. After stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was recovered. The recovered organic layer was added dropwise to a mixed solution of methanol (461 g) and ion-exchanged water (1845 g) to reprecipitate. The obtained precipitate was separated by filtration and dried at 120°C for 8 hours using a reduced pressure dryer to obtain 89.3 g of the target polymer compound
[10] (hereinafter referred to as P-6). 1 The results of H-NMR spectrum measurement are shown in Figure 6 .
[0399] The weight average molecular weight Mw of compound P-6 measured by GPC in terms of polystyrene was 23350, and the polydispersity Mw / Mn was 6.5.
[0400] [2] Preparation of film-forming composition containing a crosslinking agent and production of cured film
[0401] [Example 2-1]
[0402] P-1 (2.40 g) obtained in Example 1-1 was dissolved in cyclopentanone (hereinafter, abbreviated to CPN) (5.60 g), and 0.80 g of ATM-35E (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) as a 30 mass % CPN solution as a crosslinking agent, 0.80 g of DN-0075 (manufactured by Nippon Kayaku Co., Ltd.) as a 30 mass % CPN solution, 1.2 g of Omnirad 2959 (manufactured by IGM Resins BV) as a 10 mass % CPN solution as a photoradical polymerization initiator, 0.24 g of MEGAFACE R-40 (manufactured by DIC Corporation) as a 1 mass % CPN solution as a surfactant, and 8.97 g of CPN were added, and the dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 15 mass % (hereinafter, referred to as SP-1 solution).
[0403] The SP-1 solution was spin-coated on a 50 mm × 50 mm × 0.7 t non-alkali glass substrate at 200 rpm for 5 seconds and at 1000 rpm for 30 seconds using a spin coater, pre-dried at 100° C. for 1 minute using a hot plate, and then irradiated with 365 nm wavelength light at 400 mJ / cm using a UV irradiation device. 2 The film was irradiated with an exposure amount of , thereby obtaining a cured film (hereinafter referred to as SP-1 film).
[0404] [Example 2-2]
[0405] P-2 (1.20 g) obtained in Example 1-2 was dissolved in CPN (2.80 g), and 0.24 g of ATM-35E (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) as a 50 mass % CPN solution as a crosslinking agent, 0.24 g of DN-0075 (manufactured by Nippon Kayaku Co., Ltd.) as a 50 mass % CPN solution, 0.6 g of Omnirad 2959 (manufactured by IGM Resins BV) as a 10 mass % CPN solution as a photoradical polymerization initiator, 0.012 g of MEGAFACE R-40 (manufactured by DIC Corporation) as a 10 mass % CPN solution as a surfactant, and 4.91 g of CPN were added, and the dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 15 mass % (hereinafter referred to as SP-2 solution).
[0406] Using this SP-2 solution, a cured film (hereinafter referred to as SP-2 film) was obtained by the same procedure as in Example 2-1.
[0407] [Example 2-3]
[0408] P-3 (2.40 g) obtained in Example 1-3 was dissolved in CPN (5.60 g), and 0.80 g of ATM-35E (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) as a 30 mass % CPN solution as a crosslinking agent, 0.80 g of DN-0075 (manufactured by Nippon Kayaku Co., Ltd.) as a 30 mass % CPN solution, 1.2 g of Omnirad 2959 (manufactured by IGM Resins BV) as a 10 mass % CPN solution as a photoradical polymerization initiator, 0.24 g of MEGAFACE R-40 (manufactured by DIC Corporation) as a 1 mass % CPN solution as a surfactant, and 8.97 g of CPN were added, and the dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 15 mass % (hereinafter referred to as SP-3 solution).
[0409] Using this SP-3 solution, a cured film (hereinafter referred to as SP-3 film) was obtained by the same procedure as in Example 2-1.
[0410] [Comparative Example 2-1]
[0411] P-4 (1.20 g) obtained in Comparative Example 1-1 was dissolved in CPN (4.80 g), and 0.40 g of ATM-35E (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) as a 30 mass % CPN solution as a crosslinking agent, 0.44 g of DN-0075 (manufactured by Nippon Kayaku Co., Ltd.) as a 30 mass % CPN solution, 0.60 g of Omnirad 2959 (manufactured by IGM Resins BV) as a 10 mass % CPN solution as a photoradical polymerization initiator, 0.12 g of MEGAFACE R-40 (manufactured by DIC Corporation) as a 1 mass % CPN solution as a surfactant, and 2.49 g of CPN were added, and the dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 15 mass % (hereinafter referred to as SP-4 solution).
[0412] Using this SP-4 solution, a cured film (hereinafter referred to as SP-4 film) was obtained by the same procedure as in Example 2-1.
[0413] [Comparative Example 2-2]
[0414] P-5 (2.50 g) obtained in Comparative Example 1-2 was dissolved in CPN (5.83 g), and 0.71 g of a blocked isocyanate (BI7992, 1500 mPa·s, manufactured by BAXENDEN) in a 70% by mass PGME (propylene glycol monomethyl ether) solution as a crosslinking agent, 0.25 g of MEGAFACE R-40 (manufactured by DIC Corporation) in a 1% by mass CPNA solution as a surfactant, and 9.76 g of CPN were added, and the dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 15% by mass (hereinafter referred to as SP-5 solution).
[0415] Using this SP-5 solution, a cured film (hereinafter referred to as SP-5 film) was obtained by the same procedure as in Example 2-1.
[0416] [Solvent resistance (crack resistance) and transmittance measurement]
[0417] The substrate with the cured film prepared above was mounted on a spin coater and 1 ml of CPN was applied. Next, the cured film was exposed to the solvent by rotating at 50 rpm for 60 seconds in a manner that the liquid did not scatter from the substrate. Thereafter, the substrate was rotated at 1000 rpm for 30 seconds to remove the solvent from the substrate. Finally, after drying at 120°C for 10 seconds using a hot plate, the refractive index and film thickness were measured, the residual film rate was calculated, and the film surface was observed using an optical microscope.
[0418] The residual film rate is calculated by the following formula.
[0419] Residual film rate (%) = (film thickness after solvent exposure) ÷ (film thickness before solvent exposure) × 100
[0420] Additionally, the permeability was measured before solvent exposure.
[0421] The results of the refractive index, film thickness measurement, residual film rate and average transmittance at 300 to 800 nm are shown in Table 1, and microscopic photographs of the surfaces of the cured films of Examples 2-1 to 2-3 are shown in Table 1. Figures 7 to 9 The microscopic photographs of the cured film surfaces of Comparative Examples 2-1 to 2-2 are shown in Figures 10-11 .
[0422] Table 1
[0423]
[0424] As can be seen from Table 1, the residual film ratio of the cured films (SP-1 to SP-3 films) of Examples 2-1 to 2-3 is high. Figures 7 to 9 It was confirmed that no film cracking or fissures occurred, and it was found that the film had excellent solvent resistance (crack resistance).
[0425] On the other hand, the cured film of Comparative Example 2-1 (SP-4 film) had film cracking or cracking when it was dried on a hot plate at 120° C. for 10 seconds after solvent exposure (see Fig.10 ), and is not in a state where the refractive index and film thickness can be measured.
[0426] In addition, it was confirmed that the cured film of Comparative Example 2-2 (SP-5 film) had no film cracking or cracking, but the transmittance was lower than that of the examples (refer to Fig.11 ).
[0427] From these results, it is understood that the cured films produced from the polymer compounds obtained in Examples have excellent solvent resistance (crack resistance) and optical properties due to the presence of crosslinking sites at the polymer terminals.
[0428] [Example 3-1] Synthesis of polymer compound
[15]
[0429]
[0430] 2,2'-bis(trifluoromethyl)-4,4'-diaminediphenyl ether
[12] (218.79 g, 0.651 mol, manufactured by Wuhan Sunshine Co., Ltd.) and 1693.96 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.) were added to a 3000 mL four-necked flask, and after nitrogen substitution, 2,2'-bis(trifluoromethyl)-4,4'-diaminediphenyl ether
[12] was dissolved in DMAc by stirring. Thereafter, the flask was cooled to -10°C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine
[11] (120.00 g, 0.651 mol, manufactured by Anno Chemical (Hong Kong) Co., Ltd.) was added while confirming that the internal temperature did not exceed 0°C. After stirring for 30 minutes, 1693.96 g of DMAc was added to a 5000 mL four-necked flask, and after nitrogen substitution, the oil bath was set to 90 to 100°C, the internal temperature was adjusted to 75°C ± 5°C, and the reaction solution was added dropwise. After stirring at an internal temperature of 75°C for 1 hour, aniline
[14] (73.39 g, 0.456 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) and 2-(4-aminophenyl)ethanol
[13] (62.49 g, 0.456 mol, manufactured by Oakwood Co., Ltd.) preliminarily dissolved in 124.97 g of DMAc were added dropwise and stirred for 3 hours. Thereafter, the temperature was lowered to room temperature, n-propylamine (115.39 g, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and the mixture was stirred for 30 minutes, after which stirring was stopped. THF (2051 g), ammonium acetate (1846 g) and ion exchange water (1846 g) were added to the reaction solution and stirred for 30 minutes. After the stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was recovered. The recovered organic layer was added dropwise to a mixture of methanol (3282 g) and ion exchange water (8206 g) to reprecipitate. The obtained precipitate was separated by filtration and dried at 120°C for 8 hours using a reduced pressure dryer to obtain 235.51 g of the target polymer compound
[15] (hereinafter referred to as P-11). Compound P-11 1 The results of H-NMR spectrum measurement are shown in Fig.12 .
[0431] The weight average molecular weight Mw of compound P-11 measured by GPC in terms of polystyrene was 6070, and the polydispersity Mw / Mn was 2.6.
[0432] [Example 3-2] Synthesis of polymer compound
[16]
[0433]
[0434] In a 500 mL four-necked flask, 30.0 g of the compound P-11 synthesized in Example 3-1, 150.0 g of tetrahydrofuran (THF, manufactured by Junsei Chemical Co., Ltd.), and 3.0 g of pure water were added. After nitrogen substitution, the mixture was stirred to dissolve P-11 in THF. Thereafter, the temperature was raised to 60°C, 15.0 g of 2-isocyanatoethyl acrylate (Karenz AOI, manufactured by Showa Denko K.K.) was added, and the mixture was stirred for 3 hours. Thereafter, the temperature was lowered to room temperature, and the reaction solution was added dropwise to a mixture of methanol (158 g) and ion exchange water (396 g) to reprecipitate the mixture. The obtained precipitate was separated by filtration and dried at 80°C for 8 hours using a reduced pressure dryer to obtain 16.8 g of the target polymer compound
[16] (hereinafter referred to as P-12). 1 The results of H-NMR spectrum measurement are shown in Fig.13 .
[0435] The weight average molecular weight Mw of compound P-12 measured by GPC in terms of polystyrene was 7310, and the polydispersity Mw / Mn was 2.3.
[0436] [Comparative Example 3-1] Synthesis of polymer compound
[19]
[0437] According to the synthesis method described in International Publication No. 2016 / 194926, a polymer compound
[19] (hereinafter referred to as P-13) was synthesized.
[0438]
[0439] Compound P-13 1 The results of H-NMR spectrum measurement are shown in Fig.14 .
[0440] The weight average molecular weight Mw of compound P-13 measured by GPC in terms of polystyrene was 11580, and the polydispersity Mw / Mn was 3.7.
[0441] [Example 4-1]
[0442] P-11 (2.50 g) obtained in Example 3-1 was dissolved in PGME (5.83 g), and 0.71 g of blocked isocyanate (BI7992, 1500 mPa·s, manufactured by BAXENDEN) in the form of a 70% by mass PGME solution as a crosslinking agent, 0.25 g of MEGAFACE F-563 (manufactured by DIC Corporation) in the form of a 1% by mass PGMEA solution as a surfactant, 0.71 g of PGME, and 1.70 g of THFA (tetrahydrofurfuryl alcohol) were added, and dissolution was confirmed visually to prepare a varnish having a solid content of 30% by mass (hereinafter referred to as SP-11 solution).
[0443] The SP-11 solution was spin-coated on a 50 mm × 50 mm × 0.7 t alkali-free glass substrate at 200 rpm for 5 seconds and at 1000 rpm for 30 seconds using a spin coater, pre-dried at 100°C for 1 minute using a hot plate, and then sintered at 200°C for 5 minutes to obtain a cured film (hereinafter referred to as SP-11 film).
[0444] [Comparative Example 4-1]
[0445] P-13 (2.50 g) obtained in Comparative Example 3-1 was dissolved in CPN (5.83 g), and 0.71 g of a blocked isocyanate (BI7992, 1500 mPa·s, manufactured by BAXENDEN) in the form of a 70% by mass PGME solution as a crosslinking agent, 0.25 g of MEGAFACE R-40 (manufactured by DIC Corporation) in the form of a 1% by mass CPNA solution as a surfactant, and 9.76 g of CPN were added. The dissolution was confirmed visually to prepare a varnish having a solid content of 15% by mass (hereinafter referred to as SP-12 solution).
[0446] Using this SP-12 solution, a cured film (hereinafter referred to as SP-12 film) was obtained by the same procedure as in Example 4-1.
[0447] The refractive index, film thickness and b of the cured film obtained above were measured. * The results are shown in Table 2. In addition, the results of observing the surface of the cured film using an optical microscope are shown in Fig.15 and Fig.16 .
[0448] Table 2
[0449]
[0450] As can be seen from Table 2, since the film of Comparative Example 4-1 was thick and Compound P-13 had no crosslinking site, cracks occurred at the stage of obtaining the cured film (SP-12 film) (refer to Fig.16 ), the optical properties could not be measured. In contrast, it can be seen that the cured film of Example 4-1 (SP-11 film) has excellent crack resistance even with a thick film thickness while maintaining a high refractive index and high transparency (refer to Fig.15 ).
[0451] [Example 5-1] Synthesis of polymer compound
[102]
[0452]
[0453] P-1[4] (29.20 g) obtained in Example 1-1 and 174.84 g of cyclopentanone (CPN, manufactured by Nippon Zeon Co., Ltd.) were added to a 500 mL four-necked flask, and after nitrogen substitution, the mixture was stirred to dissolve. Thereafter, the solution was heated to an internal temperature of 60° C., 14.51 g of 2-isocyanatoethyl acrylate
[101] (AOI-VM, manufactured by Showa Denko K.K.) was added dropwise, and the mixture was stirred at an internal temperature of 60° C.±5° C. for 1 hour to prepare a CPN solution containing 30% by mass of the polymer compound
[102] (hereinafter referred to as P-21 solution).
[0454] [Example 5-2] Synthesis of polymer compound
[104]
[0455]
[0456] Into a 3000 mL four-necked flask, 1,3-phenylenediamine [2] (43.98 g, 0.407 mol, manufactured by Anno Chemical Co., Ltd.), 2,2'-bis(trifluoromethyl)-4,4'-diaminediphenyl ether
[103] (136.75 g, 0.407 mol, manufactured by Wuhan Sunshine Co., Ltd.) and 1949.90 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.) were added, and after nitrogen substitution, the 1,3-phenylenediamine [2] and 2,2'-bis(trifluoromethyl)-4,4'-diaminediphenyl ether
[103] were dissolved in DMAc by stirring. Thereafter, the mixture was cooled to -10°C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine [1] (150.00 g, 0.813 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added while confirming that the internal temperature did not reach 0°C or above. Finally, the mixture was rinsed with 114.70 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.). After stirring for 30 minutes, the reaction solution was heated to an internal temperature of 85°C ± 5°C. After stirring for 1 hour, 2-(4-aminophenyl)ethanol [3] (133.90 g, 0.976 mol, manufactured by Oakwood Co., Ltd.) dissolved in 229.40 g of DMAc (manufactured by Kanto Chemical Co., Ltd.) was added dropwise, and the mixture was stirred for 3 hours. Thereafter, 2-aminoethanol (154.02 g, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and the mixture was stirred for 30 minutes, after which the stirring was stopped. Tetrahydrofuran (THF, 1456 g), ammonium acetate (1311 g) and ion exchange water (1311 g) were added to the reaction solution and stirred for 30 minutes. After the stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was recovered. The recovered organic layer was added dropwise to methanol (1748 g) and ion exchange water (4369 g) to reprecipitate. The obtained precipitate was separated by filtration and dried at 150 ° C for 8 hours using a reduced pressure dryer to obtain 353.6 g of the target polymer compound
[104] (hereinafter referred to as P-22).
[0457] The weight average molecular weight Mw of compound P-22 measured by GPC in terms of polystyrene was 8083, and the polydispersity Mw / Mn was 3.2. 1 The results of H-NMR spectrum measurement are shown in Fig.17 .
[0458] [Example 5-3] Synthesis of polymer compound
[105]
[0459]
[0460] P-22 (polymer compound
[104] ) (30.00 g) obtained in Example 5-2 and 93.60 g of cyclopentanone (CPN, manufactured by Nippon Zeon Co., Ltd.) were added to a 300 mL four-necked flask, and after nitrogen substitution, the mixture was stirred to dissolve. Thereafter, the solution was heated to an internal temperature of 60° C., 10.11 g of 2-isocyanatoethyl acrylate (AOI-VM, manufactured by Showa Denko K.K.) was added dropwise, and the mixture was stirred at an internal temperature of 60° C.±5° C. for 1 hour to prepare a CPN solution containing 30% by mass of polymer compound
[105] (hereinafter referred to as P-23 solution).
[0461] [Example 6-1]
[0462] The P-21 solution (4.42 g) obtained in Example 5-1, 0.088 g of ATM-35E (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) and 0.088 g of DN-0075 (manufactured by Nippon Kayaku Co., Ltd.) as crosslinking agents, 0.053 g of Omnirad 2959 (manufactured by IGM Resins BV) as a photoradical polymerization initiator, 0.018 g of MEGAFACE R-40 (manufactured by DIC Corporation) as a 10 mass % CPN solution of a surfactant, and 3.86 g of CPN were added, and dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 20 mass % (hereinafter referred to as SP-21 solution).
[0463] The SP-21 solution was spin-coated on a 50 mm × 50 mm × 0.7 t non-alkali glass substrate at 200 rpm for 5 seconds and at 1000 rpm for 30 seconds using a spin coater, and pre-dried at 80° C. for 3 minutes using a hot plate, and then irradiated with 365 nm wavelength light at 200 mJ / cm using a UV irradiation device. 2 The film was irradiated with an exposure amount of , thereby obtaining a cured film (hereinafter referred to as SP-21 film).
[0464] [Solvent resistance (crack resistance) and transmittance measurement]
[0465] The substrate with the cured film prepared above was mounted on a spin coater and 1 ml of CPN was applied. Next, the cured film was exposed to the solvent by rotating at 50 rpm for 60 seconds in a manner that the liquid did not scatter from the substrate. Thereafter, the solvent was removed from the substrate by rotating at 1000 rpm for 30 seconds. Finally, after drying at 80°C for 10 seconds using a hot plate, the refractive index and film thickness were measured, the residual film rate was calculated, and the film surface was observed using an optical microscope.
[0466] The residual film rate is calculated by the following formula.
[0467] Residual film rate (%) = (film thickness after solvent exposure) ÷ (film thickness before solvent exposure) × 100
[0468] Additionally, the permeability was measured before solvent exposure.
[0469] The results of the refractive index, film thickness measurement, residual film ratio, and average transmittance at 300 to 800 nm are shown in Table 3. A microscopic photograph of the surface of the cured film of Example 6-1 is shown in Fig.18 .
[0470] Table 3
[0471]
[0472] [Example 6-2]
[0473] The P-23 solution (13.27 g) obtained in Example 5-3, 0.20 g of ATM-35E (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) and 0.20 g of DN-0075 (manufactured by Nippon Kayaku Co., Ltd.) as crosslinking agents, 0.12 g of Omnirad 2959 (manufactured by IGM Resins BV) as a photoradical polymerization initiator, 0.020 g of MEGAFACE R-40 (manufactured by DIC Corporation) as a 10% by mass CPN solution of a surfactant, and 16.19 g of CPN were added, and dissolution was confirmed by visual inspection to prepare a varnish having a solid content of 15% by mass (hereinafter referred to as SP-22 solution).
[0474] The SP-22 solution was spin-coated on a 50 mm × 50 mm × 0.7 t non-alkali glass substrate at 200 rpm for 5 seconds and at 1000 rpm for 30 seconds using a spin coater, and pre-dried at 80° C. for 3 minutes using a hot plate, and then irradiated with 365 nm wavelength light at 200 mJ / cm using a UV irradiation device. 2 The film was irradiated with an exposure amount of , thereby obtaining a cured film (hereinafter referred to as SP-22 film).
[0475] [Solvent resistance (crack resistance) and transmittance measurement]
[0476] The substrate with the cured film prepared above was mounted on a spin coater and 1 ml of CPN was applied. Next, the cured film was exposed to the solvent by rotating at 50 rpm for 60 seconds in a manner that the liquid did not scatter from the substrate. Thereafter, the solvent was removed from the substrate by rotating at 1000 rpm for 30 seconds. Finally, after drying at 80°C for 10 seconds using a hot plate, the refractive index and film thickness were measured, the residual film rate was calculated, and the film surface was observed using an optical microscope.
[0477] The residual film rate is calculated by the following formula.
[0478] Residual film rate (%) = (film thickness after solvent exposure) ÷ (film thickness before solvent exposure) × 100
[0479] Additionally, the permeability was measured before solvent exposure.
[0480] The results of the refractive index, film thickness measurement, residual film rate, and average transmittance at 300 to 800 nm are shown in Table 4. A microscopic photograph of the surface of the cured film of Example 6-2 is shown in Fig.19 .
[0481] Table 4
[0482]
Claims
1. A triazine ring-containing polymer, characterized in that: A repeating unit structure represented by the following formula (1), having at least one triazine ring terminal, at least a part of which is blocked by an aromatic amino group having a crosslinking group represented by the formula (15), wherein the crosslinking group is one or more selected from a hydroxymethyl group, a 2-hydroxyethyl group, a (meth)acryloyloxymethyl group, a (meth)acryloyloxyethyl group and a group represented by the following formulas (i-2) to (i-5), In the formula, R and R' independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group or an aralkyl group, Ar represents at least one selected from the group represented by formulae (2) to (13), In the formula, R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a sulfo group, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, R 93 and R 94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, W 1 and W 2 Independently represent single bonds, CR 95 R 96 , C=O, O, S, SO, SO2 or NR 97 , CR 95 R 96 R 95 and R 96 Each of the above independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and these atoms do not form a ring together or form a ring together, NR 97 R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group, X 1 and X 2 each independently represents a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the formula (14), In the formula, R 98 ~R 101 each independently represents a hydrogen atom, a halogen atom, a carboxyl group, a sulfo group, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, Y 1 and Y 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms, In the formula, R 102 represents a cross-linking group, In the formula, * represents a chemical bond.
2. The triazine ring-containing polymer according to claim 1, wherein The R 1 ~R 92 and R 98 ~R 101 Each of them is independently a hydrogen atom, a halogen atom or a halogenated alkyl group having 1 to 10 carbon atoms.
3. The triazine ring-containing polymer according to claim 1, wherein The aromatic amino group having a cross-linking group is represented by formula (16), In the formula, R 102 Means the same as above.
4. The triazine ring-containing polymer according to claim 1, wherein At least one aromatic ring in Ar contains at least one halogen atom or a halogenated alkyl group having 1 to 10 carbon atoms.
5. The triazine ring-containing polymer according to claim 1, wherein A portion of the triazine ring terminals are further capped with unsubstituted arylamino groups.
6. The triazine ring-containing polymer according to claim 5, wherein The unsubstituted arylamino group is represented by formula (33), 7. The triazine ring-containing polymer according to claim 1, wherein The Ar is represented by formula (17), 8. The triazine ring-containing polymer according to claim 1, wherein The Ar is represented by formula (20), 9. A film-forming composition, wherein The film-forming composition contains the triazine ring-containing polymer according to any one of claims 1 to 8 and an organic solvent.
10. The film-forming composition according to claim 9, wherein The organic solvent contains at least one selected from glycol ester solvents, ketone solvents, and ester solvents.
11. The film-forming composition according to claim 9 or 10, wherein The film-forming composition further contains a cross-linking agent.
12. The film-forming composition according to claim 11, wherein The crosslinking agent is a multifunctional (meth)acrylic compound.
13. A film, wherein The film-forming composition is obtained from the film-forming composition according to any one of claims 9 to 12.
14. An electronic device, wherein: A method of manufacturing a thin film according to claim 13 is provided, comprising a substrate and the thin film according to claim 13 formed on the substrate.
15. An optical component, wherein: A method of manufacturing a thin film according to claim 13 is provided, comprising a substrate and the thin film according to claim 13 formed on the substrate.
Citation Information
Patent Citations
Triazine ring-containing polymer and film-forming composition comprising same
WO2010128661A1
Polyamine resin and its production
JP1997087385A
Triazine dihalide containing phenolic hydroxy group, aromatic (POLY)guanamine and their composition
JP2004156001A
Triazine-ring-containing polymer and composition including same
WO2015098787A1
Triazine-ring-containing polymer and composition including same
WO2019093203A1